Structure with external support for particle adsorption bed for adsorption gas
By adopting a short-distance filled bed and a particulate adsorbent bed structure of flexible porous materials in gas separation, the problems of low pressure drop and high quality transfer rate in the prior art are solved, and the gas separation effect with low energy consumption and high economicality is achieved.
Patent Information
- Application Number
- CN202380063398.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-01
- Filing Date
- 2023-06-30
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art is difficult to achieve low pressure drop and high quality transfer rates in gas separation, especially when extracting low concentrations of CO2 from the atmosphere, resulting in high energy consumption and uneconomical system.
A particle adsorbent bed structure is adopted, which achieves low pressure drop and high quality transfer rate of airflow through a combination of a short distance filler bed and a flexible porous material. The structure includes a multi-layer flexible fabric material that encapsulates loose particulate adsorbent material and supports the adsorbent material layer through an external support structure, reducing the thickness of the adsorbent material layer and the internal support structure.
The balance between low pressure drop and high-quality transfer rate in gas separation is achieved, which reduces energy consumption and improves the economic and feasibility of the system.
Smart Images

Figure CN119855642A_ABST
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims the benefit of U.S. Provisional Patent Application No. 63 / 357,925, filed on July 1, 2022, which is incorporated herein by reference in its entirety for all purposes. Technical Field
[0002] The present disclosure relates to adsorbent bed structures for gas separation processes and the use of such structures for gas separation, for example, for separation / capture of CO2 from a gas stream. Background Art
[0003] Gas separation by adsorption has many different applications in industry, such as the removal of specific components from a gas stream, where the desired product can be either the component removed from the stream, the remaining depleted stream, or both. Thus, both trace components and major components in a gas stream can be the target of an adsorption process.
[0004] One important application is the capture of carbon dioxide (CO2) from gas streams, such as flue gases, exhaust gases, industrial waste gases or atmospheric air.
[0005] Capturing CO2 directly from the atmosphere, known as direct air capture (DAC), is one of several means of reducing anthropogenic greenhouse gas emissions and holds an attractive economic future as a non-fossil, location-independent source of CO2 for commodity markets and synthetic fuel production. Specific advantages of capturing CO2 from the atmosphere include: (i) DAC can address emissions from distributed sources (e.g., cars, airplanes), which account for a large portion of global greenhouse gas emissions and cannot currently be captured at the point of emission in an economically viable manner; (ii) DAC can address emissions from the past and can therefore produce true negative emissions; (iii) DAC systems do not need to be attached to emission sources, but are location-independent and can, for example, be located at the point where the CO2 is further processed; and (iv) if the CO2 captured from the atmosphere is used to produce synthetic hydrocarbon fuels produced from renewable energy, a truly non-fossil fuel for the transportation sector can be obtained with no or very little net CO2 emissions to the atmosphere.
[0006] Recently, some DAC methods have been developed based on various technical methods. For example, U.S. Patent No. 8,163,066B2 (Eisenberger) discloses a carbon dioxide capture / regeneration structure and technology; US2009 / 0120288 A1 (Lackner et al.) discloses a method for removing carbon dioxide from air; US2012 / 0174778 A1 (Eisenberger) discloses a carbon dioxide capture / regeneration method using a vertical lift; WO2010022339 A2 (Alberta Ltd.) discloses a carbon dioxide capture method and facility.
[0007] One particular approach is based on a cyclic adsorption / desorption process on a solid chemically functionalized adsorbent material. For example, in WO 2010 / 091831 (ETH Zurich), a structure based on an amine-functionalized solid adsorbent material and a cyclic adsorption / desorption process for extracting carbon dioxide from ambient air using the material is disclosed.
[0008] The adsorption process is carried out under the following ambient conditions: air flows through the adsorbent material, and a portion of the CO2 contained in the air is chemically bound to the amine-functionalized surface of the adsorbent. During the subsequent desorption, the material is heated to about 50-110°C. The partial pressure of carbon dioxide surrounding the adsorbent is reduced by applying a vacuum or exposing the adsorbent to a purge gas stream. Thus, the previously captured carbon dioxide is removed from the adsorbent material and obtained in a concentrated form.
[0009] In WO2012 / 168346A1 (Empa In Materialprüfungs-Und Forschungsanstalt)), an adsorbent material based on amine-functionalized cellulose is disclosed, which can be used in the above-mentioned process.
[0010] Typically, for adsorption-based gas separation processes, it is desirable to have a configuration of adsorbent material that imposes a small pressure drop on the gas stream to minimize the energy required for gas pumping while achieving maximum contact between the adsorbent and the gas stream, thereby maximizing the mass transfer rate of the component removed from the gas stream. Typical configurations include packed bed columns or fluidized beds, which are typically tens of centimeters to several meters in length, which typically impose a pressure drop of several kilopascals to several bars on the gas stream.
[0011] If trace components are removed from the gas stream, the pressure drop requirements become even more stringent. In particular, all DAC methods face a common major challenge, namely that the amount of air (volume) that must pass through any capture system to extract a certain amount of CO2 from the air is very large. The reason is that the concentration of CO2 in the atmosphere is very low, currently between 390 and 400 ppm, or about 0.04%. Therefore, in order to extract one metric ton of CO2 from the atmosphere, at least about 1,400,000 cubic meters of air must pass through the capture system. This in turn means that economically viable capture systems must have a very low pressure drop on the air stream passing through them. Otherwise, the energy requirements for air pumping will make the system uneconomical. However, any low pressure drop configuration should not compromise the mass transfer characteristics of the system.
[0012] While many materials with good properties for DAC processes are typically in granular form, their placement in fluidized beds or conventional packed bed columns, which are typically tens of centimeters to several meters in length, will generally not be feasible because the resulting pressure drop will exceed tolerable limits by one or several orders of magnitude.
[0013] On the other hand, in the field of particle filters for gas streams, in particular soot particle filters for exhaust gases, channel filter structures have been developed, generally referred to as "wall flow" filters, see for example EP 0766993 A2 (Toyota Jidosha Kabushiki Kaisha). In these structures, the gas flow enters the structure through inlet channels, passes through porous walls, and leaves the structure through outlet channels, where the soot particles are captured.
[0014] In the context of gas separation and adsorption, monomeric structures comprising adsorbent materials have also been developed, for example WO 2010 / 027929 A1 (Alstom Technology Ltd), US Pat. No. 8,202,350 B2 (SRI International). Summary of the invention
[0015] U.S. Patent No. 9,751,039 B2 assigned to Climeworks AG (hereinafter referred to as the "'039 Climeworks publication") and U.S. Patent No. 10,427,086 assigned to Climeworks AG (hereinafter referred to as the "'086 Climeworks publication") are directed to a particulate adsorbent bed structure for gas separation by adsorption, which structure can simultaneously achieve a very low pressure drop of the gas flow through the structure and a very high mass transfer rate between the gas phase and the surface of the adsorbent material. The basic principle of the structure of these publications is an arrangement as described below, in which the particles of the adsorbent material form a very short packed bed, for example 0.5 to 2.5 cm in length (please note that the length is also referred to as "thickness" in this article when viewed in the direction of the gas flow through it), through which the gas flow to be separated passes. However, such a bed arranged in a single layer would result in a very large geometry of the entire adsorption system, which is not technically and economically feasible.
[0016] In contrast, embodiments of the present disclosure relate to a particulate adsorbent bed structure for gas separation by adsorption, which can achieve a very low pressure drop of the gas flow through the structure and a very high mass transfer rate between the gas phase and the surface of the adsorbent material for efficient desorption. The basic principle of the structure according to some embodiments of the present disclosure is a setting as described below, wherein the particles of the adsorbent material form a packed bed, which has a very short distance for the gas to pass through, such as a distance of 0.1 to 2.5 cm, preferably 0.1 to 0.5 cm, and the gas flow to be separated passes through the packed bed. In some examples, a flexible porous material is provided, which contains a short-distance packed bed, which makes the particle size of the active material very small or variable. In some examples, the flexible porous material has a first hydrophobicity, which selectively excludes liquid components when a desorption medium (heat, steam) is applied. In addition to being able to move any supporting structure outside the packed bed, the flexible porous material can also construct a short-distance packed bed and allow the active material to be contained in a hydrophobic flexible porous material or a hydrophobic composite material that helps compliance. Other benefits and advantages of implementing features in accordance with the present disclosure are provided herein.
[0017] The present invention proposes a gas separation unit for separating a first gas, typically carbon dioxide, from a mixture comprising the first gas and other gases different from the first gas, the mixture typically being air or flue gas, the gas separation device being used in a cyclic adsorption / desorption process and further using loose granular adsorbent material for gas adsorption.
[0018] In the '039 Climeworks publication, the particulate adsorbent material is arranged in at least two stacked layers, and each layer comprises two sheets of flexible fabric material, which is permeable to air but impermeable to the loose particulate adsorbent material, the sheets being either mounted on a hard (rigid) frame structure or forming the layer in a self-supporting manner using spacers or distance elements between them, the sheets being arranged substantially in parallel so as to define an inlet face of the layer and an outlet face of the layer, the sheets being arranged at a distance in the range of 0.5-2.5 cm and enclosing a cavity in which the particulate adsorbent material is located. The proposed unit has a gas inlet side or gas inlet manifold through which an inflow of a gas mixture enters the unit, and a gas outlet side or gas outlet manifold through which an outflow of a gas leaves the unit, the gas path between the inflow and the outflow being restricted in the unit to pass through at least one of the layers. In other words, in any case, the gas entering the unit must pass through one of the layers, and there is no bypass under normal adsorption operation, bypass being allowed for cleaning and / or desorption processes by corresponding valves.
[0019] In the '039 Climeworks publication, the layers are arranged in a unit such that an inflow passes through an inlet face, then passes through a specific adsorbent material located in a cavity of the corresponding layer, and then leaves the corresponding layer through an outlet face (to form a gas outflow). Further, the layers are arranged such that the inlet faces of adjacent layers face each other, thereby enclosing a gas inlet channel, and such that the outlet faces face each other, thereby enclosing a gas outlet channel. The average distance between the inlet faces and / or outlet faces defining the channel (defined as the average of the distance across the surface facing each other) is in the range of 0.5-5 cm, measured along a direction substantially perpendicular to the main gas inflow direction and the main gas outflow direction, respectively. In addition, the length of the inlet face and / or outlet face along a direction parallel to the main gas inflow direction and the main gas outflow direction is at least ten times (or even 40, 50, 80 or 100 times) greater than the distance between the sheets in the layer, respectively.
[0020] The '039 Climeworks publication discloses prior art units (see, e.g., WO 2009 / 148872 A2 (Battelle Memorial Institute), U.S. Pat. No. 6,379,437 B1 (Valtion Teknillinen Tutkimuskeskus)) that use particulate adsorbent material embedded in a structured adsorbent bed through which a gas stream passes through straight-through channels. In these adsorbent bed configurations, the species to be removed from the gas stream by adsorption must be transported from the gas stream to the adsorbent material by diffusion substantially perpendicular to the flow direction of the gas stream. The gas stream in these devices is not forced to pass through a corresponding layer of adsorbent material before leaving the device. However, if very low concentration species are to be removed from the gas stream (e.g., CO2 in air), the concentration gradient from the gas stream to the adsorbent bed is small, which limits the achievable mass transfer rate and requires a long residence time, which in turn makes the process uneconomical.
[0021] By utilizing the structure disclosed in the '039 Climeworks publication, in which the gas flow is directed and forced through the channel walls composed of granular adsorbent material, the mass transfer limitations caused by diffusion can be overcome and the mass transfer rate, such as the mass transfer rate of CO2 from the gas flow to the surface of the adsorbent material, can be significantly improved relative to the prior art. At the same time, the pressure drop across the structure of the '039 Climeworks publication can be maintained at a low level compared to conventional packed column bed configurations.
[0022] Since some prior art, such as WO2009 / 148872A2 (Battelle Memorial Institute), rely on diffusion of the adsorbed material from the main gas stream to the adsorbent material layer, the thickness of the adsorbent material layer of these prior art structures is generally suggested to be very small, i.e. preferably 3 mm, to minimize mass transfer limitations. However, the '039 Climeworks publication suggests that such thin adsorbent material layers are expensive to manufacture, fragile, and not durable, and suggests that an advantage of the examples disclosed in the '039 Climeworks publication is that the structure therein can be more easily produced, i.e., the structure includes a thicker adsorbent material layer (e.g., 0.5 to 2.5 cm) than suggested in other prior art, and is implemented in a manner such that the mass transfer of the material to be adsorbed to the surface of the adsorbent material is not affected (because the gas stream passes through the adsorbent material layer), which would be the case if the diffusion-based prior art structure was implemented with a thicker, more easily producible adsorbent material layer.
[0023] The present invention improves upon this concept of the '039 Climeworks publication by constructing the layers of some embodiments to have external support features, thereby allowing thin layers of adsorbent material to be produced in an economical manner and to be easily filled without the internal structure interfering with the filling process. The external support features also enable thinner layers of adsorbent material to be formed than suggested in the '039 Climeworks publication, for example 0.1 to 0.5 cm. Additional advantages are described below.
[0024] Other prior art devices (e.g., WO 2010 / 027929 A1 (Alstom Technologies, Inc.), U.S. Pat. No. 8,202,350 B2 (Stanford Research Institute International)) utilize structures in which gas flow can be directed through a porous adsorbent material layer, but these structures are based on extruded monolithic structures, which are essentially two-dimensional structures extruded into a third dimension. In these structures, the adsorbent material is a monolithic structure, such as in gel form or deposited on the channel walls, so it is not loose. Further, these structures are typically extruded from a single material, and the extrusion process does not allow for arbitrary combinations of materials to build the structure.
[0025] The '039 Climeworks publication teaches certain advantages of structures like those used therein over other prior art extruded monolithic structures.
[0026] First, according to the '039 Climeworks publication, structures based on extruded monomers cannot represent more complex three-dimensional structures, such as stacks of individual layers of loose, specific adsorbent material confined by flexible fabric sheets. This in turn means that prior art structures cannot represent the geometry of structures of the '039 Climeworks publication, such as a heat transfer structure connected to a tube and embedded in a layer of adsorbent material enclosed between two layers of fabric material (see below).
[0027] In addition to the above, embodiments of the present disclosure provide the advantage of increased thermal conductivity and heat transfer by implementing thinner adsorbent articles than disclosed in the '039 Climeworks publication. Embodiments of the present disclosure also provide the advantage of allowing the structure to represent such complex three-dimensional structures without relying on any internal support (e.g., a portion of the frame 7 defines the geometric structure of the adsorbent layer 5 and internally supports the fabric material encapsulating the adsorbent material, as shown in Figure 2 of the '039 Climeworks publication) by implementing an external support structure that is completely external to the layer of adsorbent material and capable of supporting a layer or bed of any loose particulate adsorbent material.
[0028] Second, according to the '039 Climeworks publication, prior art structures cannot be constructed from a variety of different material combinations as easily as the structures of the '039 Climeworks publication, and do not have the corresponding advantages taught in the '039 Climeworks publication, as detailed below, such as optimized thermal mass / heat capacity, optimized thermal conductivity of heat transfer structures, etc. In particular, compared to the prior art, the addition of a flexible fabric material to encapsulate the adsorbent layer allows (i) the use of a flexible and somewhat stretchable fabric sheet to maintain the adsorbent material in the shape of a thin and uniform layer, even if the volume of the particle layer shrinks or expands to a certain extent during operation (e.g., by drying and wetting of the material); and (ii) the fabric sheets are tailored to be just impermeable to the adsorbent material particles, but at the same time very thin (0.5 to 2.5 cm thick) and impose a very low pressure drop on the airflow through them. In contrast, the attached, rigid channel walls of prior art monolithic structures (i) cannot accommodate shrinking and / or expanding sorbent packing, and (ii) will typically be thicker or less porous than optimized flexible fabric sheets to allow airflow through them because the channel walls require a denser structure to maintain their rigid structure.
[0029] In addition to the above, embodiments of the present disclosure also provide the advantage of having thinner adsorbent articles (0.1 to 0.5 cm thick) than disclosed in the '039 Climeworks publication to facilitate increased heat conduction (thermal conductivity) / heat transfer. Thinner articles can also reduce the drying or wetting time of the material. Thinner adsorbent material articles can be provided with areas or layers of reduced porosity to make the article impermeable not only to adsorbent material particles, but also to foreign (exotic) particles from the external environment. In some examples, the implementation of an external support structure helps to achieve similar or improved heat conduction without the use of any internal structure to support the loose particulate adsorbent material.
[0030] Third, according to the '039 Climeworks publication, the prior art monolithic structures may be subject to a large amount of flow bypassing the layer of adsorbent, resulting in a reduced mass transfer rate during adsorption. This is because small cavities may form in the adsorbent material (e.g., during a filling or coating process) at locations where the adsorbent contacts a rigid structure such as the walls of the monolithic structure, which reduces the resistance to gas flow at these locations and thereby induces bypass flow through these locations. In the structure of the '039 Climeworks publication, the number of walls that the adsorbent material fills the interior can be kept significantly smaller than in the prior art monolithic structures.
[0031] Fourth, according to the '039 Climeworks publication, it is proposed to use loose particulate adsorbent material in combination with a flexible fabric to define the layers, combined with a stacking arrangement with specifically selected layer thicknesses and channel widths, which allows for the provision of a very strong, low pressure drop, easy to operate and low manufacturing cost device with high efficiency of adsorption and desorption processes, wherein its geometry can be specifically tailored to specific process requirements. This is in contrast to a monolithic structure in which the adsorbent material is not provided in a loose form but in a solidified porous monolithic form, which is more restricted during the manufacturing process and does not allow for easy manufacturing, easy cleaning, re-energizing, etc. due to the fixed local arrangement of the adsorbent material in each channel or at its walls. In particular, the stacking unit of the '039 Climeworks publication can be extended essentially arbitrarily in one direction perpendicular to the main direction of the gas flow (i.e., the stacking direction) without complicating the manufacturing process. This is in contrast to the extruded monolithic structure of the prior art, which requires a larger template if the dimension perpendicular to the main direction of the gas flow is enlarged.
[0032] Furthermore, the '039 Climeworks publication text suggests that the structures therein have additional advantages over prior art extruded monolithic structures due to the above-mentioned fundamental differences in their construction.
[0033] According to the '086 Climeworks publication, the stack may be oriented so that the plane of the individual layers is a substantially horizontal plane. Thus, in this case, there are horizontal slots between the layers for the inflow of the gas mixture to enter, and horizontal slots for the outflow of the CO2-depleted gas. This substantially horizontal stack configuration may be selected to avoid the formation of holes in the layers due to movement of the adsorbent material during operation. Such holes may result in the bypassing of a large portion of the main gas flow, as they may form areas of significantly lower pressure drop.
[0034] The '086 Climeworks publication discloses that in certain circumstances it has been observed that pores may also be formed in this substantially horizontal configuration, and that more controlled pore formation may be achieved along the vertical orientation of the stack.
[0035] According to an embodiment in the '086 Climeworks publication, the layers may be placed vertically, i.e. the entire stack may be said to be rotated 90° about the main horizontal axis of the entire unit. According to this embodiment, at least two stacked layers of particulate adsorbent material, or preferably all layers in case of more than two layers, are oriented vertically, i.e. so that the plane normals of the layers are oriented horizontally, each layer comprising two sheets of flexible fabric material which is permeable to air but impermeable to loose particulate adsorbent material. In other words, along this orientation between the layers there are vertical slots for entry of the inflow of the gas mixture, and vertical slots for the outflow of the CO2-depleted gas. In this way, any repositioning / movement of the adsorbent results in a uniform bed due to the weight of the adsorbent material and the corresponding downward movement of the particles, thereby closing any pores formed in the self-sorting process. In order to avoid bypassing caused by holes formed at the upper edge of the layer, a strip preferably made of aluminum can be attached at the upper edge, which is oriented along the upper edge of the layer on the inflow and outflow faces of the layer, in contact with the outer surface of the layer, covers and thus blocks the inflow of a part of the layer and any holes that may be formed, and thus forces all inflow to pass through the adsorbent material layer containing sufficient adsorbent particles in this area. The width of the strip can be in the range of 1 to 15 cm, preferably in the range of 2 to 10 cm.
[0036] According to embodiments in the '086 Climeworks publication, intermediate rotated stack orientations are possible where the plane normals are oriented in a plane perpendicular to the inflow direction, such as an orientation where the slots for the inlet flow of the gas mixture and the slots for the outlet flow of the CO2-depleted gas are between horizontal or vertical, such as at 45°.
[0037] In addition to the above, embodiments of the present disclosure provide the advantage of housing loose particulate adsorbent material by implementing an external support structure having an internal volume in which the loose particulate adsorbent material can be disposed. For example, the external support structure can include a plurality of base portions and openings therebetween, as well as deflected portions or louvers for advantageously controlling the directionality of inflow and outflow through the external support structure. Such controlled directionality can facilitate controlled drying or wetting of the loose particulate adsorbent material, such that the particles can be uniformly wetted and uniformly dried to facilitate a more efficient cyclic adsorption and desorption process, as well as allowing the particles to be used uniformly throughout, such that they can be replaced all at once, for example, after a predetermined amount of time of use.
[0038] In some examples, the base portion and the deflected portion of the external support structure are formed from a continuous piece of rigid material. In some examples, the external support structure forms a cheese grinder, a shroud, or a fishnet structure. In some examples, multiple base portions are separate components attached or affixed to each other. In some examples, the loose particulate adsorbent material includes at least a first group of particles having a first size and a second group of particles having a second size smaller than the first size. In some examples, the first group occupies a first area within the interior volume and the second group occupies a second area within the interior volume that is different from the first area. In some examples, the external support structure has a tapered configuration.
[0039] According to a first preferred embodiment of the unit proposed in the '039 Climeworks publication, the inlet face and / or outlet face is at least 40 times longer than the distance between sheets in the layer in a direction parallel to the main gas inflow direction and the main gas outflow direction, respectively.
[0040] According to a further preferred embodiment of the '039 Climeworks publication, the flexible textile material is a woven (woven) or non-woven (woven) textile material, which is preferably based on polymer fibers or yarns, respectively, most preferably based on fibers or yarns, respectively based on PET and / or PE, or the flexible textile material is made of a cellulose-based, in particular paper-based material. The layer of flexible textile material has a preferred thickness of 25 to 500 μm.
[0041] Embodiments of the present invention improve this concept of the '039 Climeworks publication by providing a flexible nonwoven material, preferably based on a polymer material, most preferably based on a microporous polymer material, such as ePTFE or ePE. Compared with the '039 Climeworks publication that suggests the use of cellulose-based materials, particularly paper materials, the use of one or more of these materials provides a variety of advantages. The nonwoven microporous material of the present invention (e.g., nonwoven and microporous ePTFE or ePE) can provide at least one of the following: 1) hydrophobicity, 2) a reduction in porosity, and / or 3) a fabric material that is both inert and durable. For example, the reduction in porosity prevents particles larger than a predetermined size from passing through the layer. For example, the total thickness of the flexible nonwoven material layer is 25 to 500 μm, preferably between about 25 μm to about 50 μm, between about 50 μm to about 75 μm, between about 75 μm to about 100 μm, or any other suitable value or range therebetween.
[0042] Preferably, according to the '039 Climeworks publication, more than 5, preferably more than 10, most preferably more than 20 layers are stacked substantially parallel to each other in the unit, preferably by using stacking of corresponding frames; and / or stacked at a relative inclination angle in the range of 0.2-15°, preferably in the range of 0.5-10°. In the latter case, the corresponding inlet channels can be arranged to converge in the main gas inflow direction, while the corresponding outlet channels widen in the main gas outflow direction. In this case, the inlet channels can be closed at their downstream ends substantially by the side edges of adjacent layers in (direct) contact with each other, and the outlet channels can be closed at their upstream ends by the side edges of adjacent layers. In other words, looking at the unit along a plane perpendicular to the direction of the gas flow and parallel to the layers, the layers are arranged in a zigzag shape.
[0043] The layers in the '039 Climeworks publication may be substantially planar structures stacked parallel to one another, or the layers may be substantially cylindrical or elliptical structures, most preferably disposed concentrically with one another.
[0044] The spacers of the '039 Climeworks publication may be located within the layers to define the distance between the surfaces of the layers, the spacers preferably being rigid bars or rail structures, most preferably T, H, C or Z bar structures, or provided by joints and / or seams between sheets.
[0045] At least one layer, preferably a majority of the layers, and most preferably all of the layers of the '039 Climeworks publication may be provided with primary heat exchange elements, preferably in the form of tubes containing a heat exchange fluid, most preferably in combination with secondary heat exchange elements to increase heat transfer between the adsorbent material and the heat exchange elements.
[0046] According to the '086 Climeworks publication, the primary heat exchange element may be a plurality of serpentine tubes for heat exchange fluid disposed within a rigid rectangular circumferential frame structure and within a cavity, wherein the plurality of tubes on the non-curved portions thereof are all disposed substantially parallel to a first pair of mutually parallel metal profiles forming the rigid frame structure.
[0047] The tubes in the '086 Climeworks publication can be in thermal contact with a secondary heat exchange element, which is in the form of a plurality of metal sheets, which are arranged parallel to each other and substantially perpendicular to the main plane of the rigid frame structure and perpendicular to the tubes (non-bent parts of the tubes), which extend in a continuous manner between the first pair of mutually parallel metal profiles, and the secondary heat exchange element in the form of a metal sheet is provided with a plurality of holes, through which a plurality of tubes pass.
[0048] The tubes of the primary heat exchange element in the '086 Climeworks publication are preferably metal tubes, preferably aluminum or copper tubes. These tubes may have an inner diameter in the range of 3-20 mm, preferably 5-12 mm, and / or an outer diameter in the range of 4-24 mm, preferably 6.2-14 mm.
[0049] The tubes of the primary heat exchange element of the '086 Climeworks publication are typically spaced apart, while extending in parallel, by a distance (x) in the range of 10 to 168 mm, preferably in the range of 15.5 to 98 mm.
[0050] According to the '086 Climeworks publication, if forming a secondary heat exchange element, the thickness of the metal sheet is in the range of 0.1 to 0.4 mm, preferably in the range of 0.12 to 0.18 mm.
[0051] According to the '086 Climeworks publication, if forming a secondary heat exchange element, the height (h) of the metal sheet, measured perpendicularly to the extension direction of the tube, is in the range of 3-50 mm, preferably in the range of 8-22 mm.
[0052] According to the '086 Climeworks publication, if forming a secondary heat exchange element, the length of the metal sheet is less than 20 mm, preferably 5 mm shorter than the distance between corresponding pairs of metal profiles arranged in parallel pairs forming the rigid rectangular circumferential frame structure.
[0053] The metal sheets of the '086 Climeworks publication are preferably made of aluminum.
[0054] Typically, if forming a secondary heat exchange element, the metal sheets of the '086 Climeworks publication are spaced apart by a distance (d) in the range of 1-6 mm, preferably in the range of 3.5-5.5 mm.
[0055] According to the '086 Climeworks publication, the above values are the best compromise in terms of the dimensions of the tubes and metal sheets, which allow good (inter)penetration of the particulate adsorbent material, also allowing filling of the structure during manufacturing, and on the other hand allowing sufficient porosity for air to pass through the layer and allow the heat transfer process to be as efficient as possible during the heating and cooling steps during cyclic temperature swing CO2 capture.
[0056] According to the '086 Climeworks publication, the pipes forming the primary heat exchange pipes may also have a non-circular cross-section (flat shape) at least in some sections (partially). Specifically, a first outer diameter of the cross section of the pipe in a direction perpendicular to the plane of the rigid framework structure layer may be at least twice the second outer diameter of the cross section of the pipe in a longitudinal direction. By providing "slender" inter-pipe spaces in the plane of the rigid framework structure layers, the pipes appear like upright partitions in the cavity, providing substantially flat surfaces at the faces of adjacent pipes, thereby allowing for the most efficient attachment and heat exchange with secondary heat exchange elements in the form of heat exchange metal sheets and / or adsorbents, as will be discussed below.
[0057] According to the '086 Climeworks publication, this flat tube design results in two significant advantages over heat exchange tubes having a circular cross-section: First, because the tubes block a smaller portion of the flow cross-sectional area, the area available for gas flow through the plane of the sheet of flexible fabric material is much larger. This results in a reduced pressure drop for the gas flow. Second, compared to prior art designs having a circular tube cross-section, the tubes can be spaced closer to each other while the area available for gas flow remains larger than in prior art designs. This results in an optimized heat transfer design because the heat transfer distance between the flat tubes through the adsorbent material is reduced.
[0058] The flat tubes in the '086 Climeworks publication may further be in thermal contact with metal sheets that form secondary heat exchange elements and are arranged substantially perpendicular to the main plane of the rigid frame structure and swing between pairs of adjacent flat tubes to contact them for thermal contact. In other words, these metal sheets either swing in a wave-like manner between adjacent flat tubes and contact the flat small diameter surface, or zigzag (travel) between adjacent flat tubes and contact the flat small diameter surface.
[0059] As an alternative or in addition to the metal sheets, the flat tubes may be held in place by spacers arranged substantially perpendicular to the main plane of the frame and extending at least between pairs of adjacent flat tubes, as disclosed in the '086 Climeworks publication.
[0060] The primary heat exchange element and / or the secondary heat exchange element may also be used as the frame structure and / or sheet material in the '039 Climeworks publication. The primary heat exchange element and / or the secondary heat exchange element may be integrated into the frame structure to stiffen it and prevent sagging. Further, the primary heat exchange element and / or the secondary heat exchange element may be combined with a fabric material to prevent bulging when filled with adsorbent material and stiffen the frame structure in some combination.
[0061] Furthermore, the primary heat exchange elements and / or the secondary heat exchange elements of the '039 Climeworks publication may be based on an expanded material, preferably an expanded metal, such as a corrugated expanded metal.
[0062] The loose particulate adsorbent material in the '039 Climeworks publication and the '086 Climeworks publication is preferably an amine-modified particulate material, preferably based on cellulose, more preferably based on a weakly basic ion exchange resin, especially a polystyrene matrix material modified with amine groups, especially primary amine groups, or based on amine-modified nanofibrillated cellulose, in each case preferably having an average particle size in the range of 60 to 1200 μm, for adsorbing carbon dioxide.
[0063] In contrast, the loose particulate adsorbent material of the present invention may be an amine-modified particulate material having a particle size of 2-1200 μm, preferably a particle size of 5-50 μm, for example to reduce the overall thickness of the adsorbent material layer or its structure, which provides the advantage of reducing the adsorption / desorption cycle time, as further explained herein.
[0064] The framework of the '039 Climeworks publication may be provided with holes into which loose specific adsorbent material may be filled, and the holes in the holes may be encapsulated after being filled with the adsorbent material.
[0065] The unit of the '039 Climeworks disclosure may also include a surrounding enclosure or cage, preferably made of a flexible (bag-like) or rigid (frame cage-like) material, which is airtight except for a gas inlet opening for the inflow and a gas outlet opening for the outflow, and is preferably attached to a vacuum unit for the desorption process, wherein preferably the inlet opening and / or the outlet opening are provided with a controllable cover or valve for changing between adsorption and desorption phases. This feature facilitates operating the structure of the '039 Climeworks disclosure in a cyclic adsorption / desorption process, wherein during adsorption, air flows through the structure through the cover or valve, and during desorption, the structure is sealed relative to the environment and can be heated and / or exposed to reduced or increased pressure and / or exposed to a different atmosphere, such as a purge gas.
[0066] The individual sheets of each layer in the '039 Climeworks publication are preferably located at a distance in the range of 0.5-1.5 cm, and / or wherein the average distance between adjacent inlet faces and / or outlet faces (i.e., the width of the channel) measured in a direction substantially perpendicular to the main gas inflow direction and the main gas outflow direction, respectively, is in the range of 0.5-1.5 cm.
[0067] Additionally, the '039 Climeworks publication relates to the use of such units to extract carbon dioxide from air and / or to extract flue gases from exhaust gases.
[0068] Further embodiments of the '039 Climeworks publication are further described below and in the dependent claims.
[0069] The stack formed by the multiple layers of adsorbent material in the '039 Climeworks publication can have a variety of geometric shapes, such as rectangular (FIGs. 1, 6 of the '039 Climeworks publication), cubic, or cylindrical (FIG. 7 of the '039 Climeworks publication). The gas inlet side through which the gas flow enters the structure can be formed by a gas inlet manifold, or can be open to the surrounding environment. The gas outlet side through which the gas flow leaves the structure can be formed by a gas outlet manifold, or can be open to the surrounding environment.
[0070] According to one embodiment of the '039 Climeworks publication, two layers of flexible fabric material encapsulating a particulate adsorbent material are mounted on a rigid frame structure (e.g. produced by injection molding of a plastic material) which forms the geometry of the adsorbent layer. (Figure 1 of the '039 Climeworks publication)
[0071] According to another embodiment of the '039 Climeworks publication, two layers of preferably flexible fabric material form the adsorbent material layer, not using a rigid structure, but by using a plurality of spacers or distance members between the two layers of fabric material. Those spacers can have various geometric shapes and can be made of various materials. In one embodiment, the distance members can be small plastic cylinders of the same length as the thickness of the adsorbent layer. In another embodiment, the spacers can be made of filament yarns, and the two layers of fabric can be held together by sewing.
[0072] For the examples disclosed in the '039 Climeworks publication, one advantage of the '039 Climeworks publication teaching is that by stacking very thin adsorbent layers (0.5 to 2.5 cm thick), the particulate adsorbent material can be arranged in a geometrically compact form with a relatively small flow path length of the gas through the adsorbent material. The '039 Climeworks publication applies the principles known from wall-flow type monolithic structures of arranging very large surface areas in a compact form to structures constructed from particulate materials.
[0073] In addition to the above, embodiments of the present disclosure provide the advantage of making the adsorbent article more compact and further shortening the length of the flow path of the gas through the adsorbent material by implementing thinner materials with a thickness between 0.1 and 0.5 cm, as disclosed herein. In addition, the present disclosure provides the advantage of a more controlled air path, for example, by providing deflected portions or baffles in the external support structure to control the directionality of the air path, which can help achieve a shorter flow path than otherwise possible.
[0074] For example, according to the '039 Climeworks publication, if the 1m 3 The adsorbent material is arranged in a single packed bed with a bed length of 1 cm, and the cross-sectional area of the bed is 100 m 2 , for example 10m x 10m. On the other hand, if the same amount of material is arranged in 100 stacked layers, each layer is 1cm thick and has an area of 1m 2 , with 1 cm wide inlet and outlet channels between each layer, the total stack size is 1m×1m×2m, which is more compact and therefore takes up less space. At the same time, the stacking arrangement significantly helps with gas distribution. Although the gas flow is evenly distributed to 100m 2 The bottom region of a large bed would require an excessive amount of tubing, but the tubing required to direct the gas flow to the inlet of a 1 m x 1 m x 2 m stack is relatively small. This consideration also dictates that, in order to benefit from the compactness of a stacked arrangement, the length of the adsorbent layer and the length of the gas inlet and outlet channels along the main direction of gas flow (parallel to the adsorbent layer) need to be significantly greater than the thickness of the adsorbent layer, e.g., at least 10 times greater than the thickness of the adsorbent layer according to the '039 Climeworks publication.
[0075] Another advantage suggested by '039Climeworks for the examples in the '039Climeworks publication is that, because the structure is made of a stack of individual layers (as opposed to other prior art flow structures that are, for example, extruded or cast from a single material), the structure can be constructed from a variety of materials and various combinations of materials. For example, the frame defining the geometry of the adsorbent material layer can be made from a hard, mechanically stable, lightweight material, while the two layers of preferably flexible fabric material encapsulating the adsorbent material layer can be made from different materials having the desired permeability characteristics to the airflow and adsorbent material particles. For example, while the material forming the geometry of the adsorbent layer can be a hard material, the material forming the two fabric layers encapsulating the adsorbent material layer can be a flexible material, which can allow the adsorbent material layer to have different forms, such as a bag-like form with a curved outer surface. It can further compensate for changes in the fill volume of the adsorbent material due to shrinkage or expansion of the particles during the above-mentioned process. This in turn allows the adsorbent material layer to have several different geometries that cannot be obtained by encapsulating a hard layer of adsorbent material. Also, according to the '039 Climeworks publication, the heat transfer structure contained within the adsorbent material layer may be made of another material having good thermal properties, such as high thermal conductivity.
[0076] In addition to the above, embodiments of the present disclosure provide the advantage of improving the efficiency of the adsorption and desorption processes by implementing thinner individual layers using an external support structure, wherein the external support structure can be rigid to provide support and positioned completely outside the individual layers. The external support structure can also be configured to control the directionality of the airflow, such as the air path and inflow / outflow through the layer, to improve the efficiency of the adsorption and desorption processes.
[0077] According to one aspect of the '039Climeworks disclosure, a combination of materials can be used that minimizes the thermal mass of a single structure. The '039Climeworks disclosure suggests that such a design is advantageous if the structure is used during a cyclic temperature swing process because it can reduce energy consumption. According to a preferred embodiment of the '039Climeworks disclosure, the disclosed structure is used to extract CO2 from the atmosphere. In this preferred embodiment, the structure operates in a cyclic adsorption / desorption process, wherein during the adsorption step, air is ventilated through the structure and a portion of the CO2 contained in the air is bound to the surface of the adsorbent material contained in the adsorbent material layer of the structure. Under typical process conditions, the adsorption step is carried out for 2 hours, an average of about 40% of the CO2 in the air stream is extracted, and each dm 3 The adsorbent material adsorbs about 0.3 mol CO2. Based on these values, the air velocity u through the adsorbent layer 空气 It can be determined as a linear function of the adsorbent layer thickness d, roughly: u 空气 (m / s)=0.03m / (s*cm)*d(cm)
[0078] In addition to the above, embodiments of the present disclosure provide advantages of improved cyclic temperature swing processes, such as by using thinner layers of adsorbent material (e.g., 0.1 to 0.5 cm thick), using hydrophobic materials to form material layers, and / or using external support structures having devices (i.e., deflected portions or shields) for controlling the directionality of inflow and outflow through layers as disclosed herein to reduce the time required for each adsorption / desorption cycle (e.g., to less than 2 hours per cycle or less than 1 hour per cycle, according to some embodiments).
[0079] Meanwhile, for typical adsorbent materials, the pressure drop across the adsorbent layer, Δp, is roughly a linear function of the air velocity and the adsorbent layer thickness, as shown below: Δp=1.2kPa / cm / (m / s)*u 空气 (m / s)*d(cm)
[0080] Thus, the total pressure drop increases with the square of the adsorbent layer thickness. For a thickness of 1 cm, the resulting total pressure drop is about 36 Pa, while for a thickness of 5 cm, the resulting total pressure drop is about 900 Pa, which is about an order of magnitude too large for economical DAC applications. On the lower limit, adsorbent layer thicknesses much below 0.5 cm are very expensive to manufacture. This in turn means that the relatively narrow range of preferred adsorbent layer thicknesses of 0.5 to 2.5 cm is an important aspect of the '039 Climeworks publication.
[0081] In addition to the above, in embodiments of the present disclosure, an adsorbent layer having a thickness of about 0.1 to 0.5 cm is provided, which is thinner than the preferred thickness of 0.5 to 2.5 cm disclosed in the '039 Climeworks publication, to reduce the adsorption / desorption cycle time and increase the number of cycles that can be completed within a predetermined amount of time. The thinner adsorbent layer can be combined with a particulate adsorbent bed having smaller adsorbent particles therein to reduce cycle time and facilitate uniform wetting and drying of the adsorbent particles. For example, these advantages can be provided by the same pressure drop Δp through the adsorbent layer as disclosed in the '039 Climeworks publication.
[0082] As now disclosed herein, adsorbent layers having a thickness below 0.5 cm, such as between 0.1 cm and 0.5 cm, advantageously have thinner walls, which helps to contain additional volume for the adsorbent material within the container. For example, implementing a thinner adsorbent material layer in the range between 0.1 cm and 0.5 cm helps to reduce the pressure drop across the adsorbent material layer. Thinner adsorbent material layers are possible because the microporous structure in the adsorbent material is tighter, thereby allowing the use of smaller adsorbent particles, resulting in a reduction in the thickness of the layer without increasing manufacturing costs, as described in the '039 Climeworks publication. In fact, having a thickness greater than 2.0 cm may be disadvantageous because the pressure drop between two opposing surfaces of the adsorbent material layer increases. For example, a thicker adsorbent layer may require the use of a larger adsorbent particle size (which will be loosely packed and allow air to flow through and through it). The thinner structure may also achieve one or more of the following: (a) facilitate increased diffusion of CO2 into the structure, (b) allow more thin adsorbent sheets to be positioned within the volume, (c) optimize the structure for adsorbent mass and improve cycle efficiency, and (d) reduce diffusion resistance for the same flow rate of air through the structure. These larger particles have less surface area and less kinetic energy than smaller particles of the same material. Microporous materials such as ePTFE and ePE enable the use of smaller particle sizes and will allow the use of thinner adsorbent layers with greater surface area and improved performance. For example, end caps of any suitable configuration may be provided or mounted on the structure to facilitate removal of the layer of adsorbent material from the external support structure, even if the layer itself is less than 0.5 cm thick.
[0083] The use of the structure disclosed in the '039 Climeworks publication for extracting CO2 from the atmosphere is a preferred embodiment of the '039 Climeworks publication. The structure of the '039 Climeworks publication is also used in other applications, such as separating CO2 from flue gases, exhaust gases, industrial waste gases or other components other than CO2 from these or other gas streams.
[0084] According to one embodiment of the '039 Climeworks publication, the gas inlet and outlet channels are formed by a rigid frame structure (e.g., produced by injection molding of a plastic material) that forms the geometry of the adsorbent layer, on which two layers of flexible fabric material encapsulating the adsorbent material are further mounted. An important function of the rigid frame structure in this embodiment is that they provide enough surface (e.g., rods, bars, or track structures within the frame) to glue or weld the flexible fabric material, which in turn provides enough tension for the flexible fabric material to keep the adsorbent material in a layer with a relatively uniform thickness. The rigid frame structure may include a spacer that fixes the distance between the two frame structures, which is also the width of the inlet and outlet channels between the two frame structures. The rigid frame structure may also include a structure that seals the inlet and outlet channels toward the outside of the structure (except for their inlet / outlet surfaces). The inlet and outlet channels may be formed by stacking the frames on top of each other.
[0085] According to one embodiment of the '039 Climeworks publication, the particulate adsorbent layers are stacked in a zigzag manner, as described above (Figure 2 of the '039 Climeworks publication). As suggested in the '039 Climeworks publication, an advantage of this embodiment is that the gas velocity in the gas inlet and gas outlet channels is more uniform along the main flow direction of the gas flow than in the case of gas inlet and gas outlet channels of constant width. This is because the gas volume flow rate decreases along the gas inlet channel along the main flow direction because part of the gas flow leaves the gas inlet channel through the adsorbent material layer. At the same time, the volume flow rate increases along the gas outlet channel along the main flow direction because part of the gas flow enters the outlet channel from the adsorbent material layer. This embodiment makes the pressure gradient distribution across the adsorbent material layer in the structure of the present invention more uniform, and therefore the flow distribution through the adsorbent material layer is more uniform, which ensures the most efficient utilization of the adsorbent material during the adsorption process.
[0086] In addition to the above, embodiments of the present disclosure provide the advantage of implementing deflected sections or shields in the external support to further improve the uniformity of the flow direction. The shields can have different sizes and deflection angles throughout the frame. The sizes and angles are derived from fluid analysis of the airflow entering the system and passing through the adsorbent material layer to optimize performance.
[0087] According to a preferred embodiment of the '039 Climeworks publication, the structure includes a primary heat transfer structure and preferably a secondary heat transfer structure, which are preferably placed inside or at the side of the adsorbent material layer (Figure 3 of the '039 Climeworks publication). The heat transfer structure can be made of a material with high thermal conductivity, such as a metal, such as copper or aluminum. For example, the secondary heat transfer structure can be composed of one or more permeable structural layers or sheets placed inside the adsorbent material. These sheets can, for example, be composed of perforated metal, expanded metal, metal mesh, metal grid or lattice. Further, the secondary heat transfer structure can be composed of a honeycomb structure, such as an aluminum honeycomb structure.
[0088] One possible secondary heat transfer structure for the adsorbent material layer of the '039 Climeworks publication and the '086 Climeworks publication is based on fins or metal sheets, preferably aligned substantially perpendicular to the plane of the particulate adsorbent material layer. If the metal sheets are aligned substantially horizontally, the fins are aligned vertically. If the particulate adsorbent material layer is substantially vertical, the fins or metal sheets of the secondary heat transfer structure are oriented horizontally. In this concept, the vertical fins forming the secondary heat transfer structure are mechanically coupled to the primary heat transfer structure, which preferably comprises or consists of aluminum tubing.
[0089] FIG. 20 of the '039 Climeworks publication schematically illustrates vertical fins perpendicular to the plane of the fabric material incorporated as secondary heat transfer structures in the adsorbent material layer and frame. First, because most fin and tube heat exchangers are limited in heat transfer on the gas side, the surface area of their fins is very large, which requires narrow gaps between the fins on the order of 1 mm. As determined by thermal simulations, the preferred conduction distance in adsorbent materials for DAC applications is about 3-8 mm or 5 mm, resulting in a distance between heat transfer structures of preferably 4-15 mm, more preferably 5-12 mm or 10 mm, and the 5-12 mm or 10 mm spacing between the fins of the secondary heat transfer structures represents a good and preferred compromise between the thermal mass and heat transfer effect of the heat transfer structures, and makes these structures therefore suitable for DAC applications. Further, the spacing between fins that is commonly used is about 1 mm, which may indicate that the effective airflow cross-sectional area is limited, thereby potentially producing airflow velocities and pressure drops that are not suitable for DAC applications. By increasing the fin pitch of the secondary heat transfer structure to the above defined range, the effective cross-sectional area of the air flow through the adsorbent material layer can be increased, thereby reducing the air flow velocity and reducing the pressure drop across the adsorbent material layer to a level that is feasible for DAC applications. This may be an important requirement for some DAC applications.
[0090] Secondly, by incorporating fins as secondary heat transfer structures in the frames, the thickness of the adsorbent material layer in the '039 Climeworks publication can be increased because there is no heat transfer limitation in the vertical direction. In this way, as long as the pressure drop through the adsorbent material layer is maintained within an acceptable range, the thickness of the adsorbent material layer can be increased, thereby reducing the number of frames for a given stack height and the stacking cost and thermal mass per unit of adsorbent material. The diameter of the tubes of the primary heat transfer structure can be thinner than the adsorbent material layer, as shown in Figure 20 of the '039 Climeworks publication. In this construction, the tubes are not combined with the fabric layer and form a large number of separate adsorbent cells in each frame. A positive result is that since the adsorbent can bypass the tubes, the frame can be filled with adsorbent material through a hole in one corner. To support this filling concept, the vertical fins of the secondary heat transfer structure (10) can be perforated (see Figure 20a of the '039 Climeworks publication) to allow adsorbent material to pass between them. Thin perforated metal sheets are known, for example, from the production of perforated metal honeycomb structures. This design represents a further improvement over the above-mentioned planar secondary heat transfer structures placed in the middle of the frame, which typically limit the maximum adsorbent material layer thickness to about 10 mm. Further, current designs require multiple adsorbent material filling ports.
[0091] Third, due to the spacing of the fins of the secondary heat transfer structure, the fabric material in the '039 Climeworks publication can be bonded to the fins over a short distance, thereby preventing bulging under the weight of the filled adsorbent. The positive result is that the inlet and outlet channels have a more defined and regular geometry. This is in contrast to other designs in which the fabric material can be bonded at most every 100 mm, beyond which bulging under the weight of the adsorbent material is essentially unavoidable and may block the inlet / outlet channels. Further structural stability can be achieved by aligning the fins along the longer edges of the frame and bonding them to the fabric material. In this way, the fins of the secondary heat transfer structure act as a core with lateral struts that transfer loads to the tensioned fabric material. This significantly improves the stiffness and stability of the frame.
[0092] The production technology of the fin and tube heat exchanger in the '039 Climeworks publication involves placing the tubes into the holes of the fins and partially expanding the tubes so that plastic deformation occurs in the tubes and fins, thereby attaching the fins to the tubes. Typically, one fin spans multiple passages of the tubes. This is achieved by placing the fins on multiple straight tubes, expanding the tubes and connecting the tube sections with welded or brazed elbow connectors. In this way, a strong mechanical connection and a good thermal connection are achieved in a multi-pass fin and tube heat exchanger. The process has been industrially automated and can also be adapted for DAC applications.
[0093] An alternative manufacturing method for the structure to be used for the DAC is described below and is shown in Figure 21 of the '039 Climeworks publication. As in the conventional production process, the fin groups of the secondary heat transfer structure are assembled on the tubes of the primary heat transfer structure with a spacing of "L" between each group (Figure 21a of the '039 Climeworks publication). The fins are attached to the tubes using conventional tube expansion techniques. Thereafter, the tubes with the assembled fins can be bent into the form of the desired primary heat transfer structure in a conventional frame design (Figure 21b of the '039 Climeworks publication). In the bent state, there are small gaps between the fins, which do not significantly affect the heat transfer into the adsorbent. Since there are no fins in the bent portions, they can be placed into the frame outline according to the current frame design. In this way, a tube-fin heat exchanger can be made from a continuous tube and no welding or brazing processes are required.
[0094] Furthermore, the thicker adsorbent material layer in the '039 Climeworks publication requires a thicker frame profile, which allows for a larger filling hole, thereby significantly speeding up the filling speed of the adsorbent material. For a 10 mm C-profile frame, the filling hole may be 6 mm, and the resulting filling tube inner diameter may be 4 mm, which may represent a significant restriction to the flow of the adsorbent material during filling and a corresponding increase in the filling time of the adsorbent material. A 20 mm frame thickness may support the use of a 16 mm filling hole, for example with an inner diameter of 14 mm.
[0095] Furthermore, the secondary heat transfer structures of the '039 Climeworks publication may be composed of a particulate material having good thermal conductivity mixed with an adsorbent material.
[0096] The primary heat transfer structure of the '039 Climeworks publication may be contained in or connected to a secondary heat exchange structure, which may be a pipe through which a heat transfer fluid, such as water or a water / ethylene glycol mixture, can flow (FIGs. 3 and 4 of the '039 Climeworks publication). The pipe may be, for example, a curved copper or aluminum pipe or a rubber or plastic hose. With the heat transfer fluid, the heat transfer structure may be rapidly heated or cooled by an external heating or cooling source, such as a tank of hot or cold heat transfer fluid.
[0097] The heat transfer structure incorporated in the structure facilitates operation of the unit of the '039 Climeworks publication during cyclic adsorption / desorption periods that include thermal swings, as it allows rapid heating and cooling of the particulate adsorbent material between the various steps of the adsorption / desorption cycle. The possibility of transferring heat from and to the heat transfer structure via a heat transfer fluid passing through the tubing provides an important interface for other process or facility components incorporating the unit of the '039 Climeworks publication, as it allows the incorporation of various heating and cooling sources, typically provided in the form of streams of hot or cold fluids.
[0098] Preferably, the heat transfer structure included in the structure of the '039 Climeworks publication is in good thermal contact with substantially all of the particulate adsorbent material in each adsorbent material layer so that the heating and cooling times of the adsorbent material are kept to a minimum. Preferably, the heat transfer structure is constructed and incorporated into the structure of the '039 Climeworks publication in such a manner that substantially all of the adsorbent material can be heated or cooled by 75K (Kelvin) in less than 60 minutes, more preferably in less than 20 minutes.
[0099] If the main heat exchange structure in the '039 Climeworks publication is composed of pipe fittings contained in each layer, the ends of the pipes can be connected to cylindrical elements contained in each frame structure. When the layers are stacked, these cylindrical elements can preferably be connected to each other using O-rings to form a skeleton (trunk) pipeline to transfer the heat transfer fluid to and from the pipes in each layer. The diameter of the skeleton pipeline formed by individual cylindrical elements can range from 1 to 5 cm. Further, the pipe fittings of the main heat exchange structure and the secondary heat exchange structure can be directly included in the frame structure during the injection molding process. According to another embodiment of the '039 Climeworks publication, the main heat exchange structure of each adsorbent layer can be connected to a feed and return distributor of the heat transfer fluid, which itself is connected to the heat transfer fluid feed and return pipelines. According to another embodiment of the '039 Climeworks publication, the heat transfer structure placed in the adsorbent material layer forms a partial or complete geometry of the granular adsorbent material layer and / or serves as a support for two layers of flexible fabric material encapsulating the adsorbent material layer. For example, the heat transfer structure can be made of corrugated expanded metal, wherein the lower and upper peaks of the corrugations serve as mounting surfaces for the fabric material (FIG. 5 of the '039 Climeworks publication). As another example, the heat transfer structure can be made of an aluminum honeycomb structure having the same thickness as the adsorbent material. Two layers of fabric material can be attached to the honeycomb structure by, for example, gluing or welding. As suggested in the '039 Climeworks publication, an advantage of this embodiment is that, since the heat transfer structure simultaneously satisfies two functions (heat transfer and support of the fabric layer), the amount of material required to form the exemplary structure of the '039 Climeworks publication is minimized. According to the '039 Climeworks publication, this in turn results in minimizing the thermal mass of the structure of this embodiment, thereby reducing the energy consumption of the heating structure.
[0100] In addition to the above, the present disclosure provides the advantage of further reducing the amount of material required to form the structure, particularly by implementing a thinner adsorbent material layer having a thickness of less than 0.5 cm (e.g., from 0.1 cm to 0.5 cm), as compared to the adsorbent layer in the '039 Climeworks publication (whose preferred adsorbent layer thickness is, for example, 0.5 to 2.5 cm), thereby further reducing the amount of adsorbent material layer disposed in the structure.
[0101] According to one embodiment of the '039 Climeworks publication, the adsorbent material layers have a rectangular shape, e.g., a rectangular shape with a side length of 1 m and a thickness of 1 cm, and the stack formed by these layers has the form of a rectangular block shape, e.g., 1 m×1 m×1 m ( FIG. 6 of the '039 Climeworks publication).
[0102] According to another embodiment of the '039 Climeworks publication, the adsorbent material layer has the shape of a disk with a central hole, for example, a disk with a diameter of 1.5 m and a central hole with a diameter of 0.6 m, and the stack formed by these layers has a cylindrical shape, for example, with a diameter of 1.5 m and a length of 2.5 m (FIG. 7 of the '039 Climeworks publication). In this embodiment, the gas inlet manifold is formed by the central hole of the stack, and the gas outlet manifold may have the form of an annulus surrounding the cylindrical stack.
[0103] According to another embodiment of the '039 Climeworks publication, the layers of adsorbent material have the shape of concentric rings, and the stack formed by these layers has a cylindrical shape, for example, with a diameter of 1.5 m and a length of 2.5 m ( FIG. 8 of the '039 Climeworks publication).
[0104] According to one embodiment of the '039 Climeworks publication, the layer of flexible fabric material encapsulating the layer of adsorbent material simultaneously functions as a particle filter that prevents particles in the inlet gas stream, such as dust particles, from separating from the adsorbent material. The '039 Climeworks publication suggests that this embodiment may be advantageous for applications where filtering of the inlet gas stream is required to protect the adsorbent material, such as the adsorption of CO2 from the atmosphere. Thus, in this embodiment, no additional filtering structure is required. Since the surface area of the fabric sheets is very large and the flow rate through them is relatively low (see above), the pressure accumulated on the sheets due to dust loading is relatively small.
[0105] In addition to the above, embodiments of the present disclosure provide the advantage that smaller particles than were possible in the '039 Climeworks disclosure can be blocked by implementing a nonwoven microporous material (e.g., nonwoven and microporous ePTFE or ePE) in the adsorbent material layer, which reduces the porosity of the layer to prevent foreign particles of a predetermined size from completely passing through the layer. The hydrophobic material of the present disclosure can also help prevent liquid water from entering the material layer while allowing water vapor to pass through.
[0106] According to one aspect of the '039 Climeworks publication, the pressure drop of a gas flow through gas inlet and outlet passages enclosed between the inlet and outlet faces of a layer of adsorbent material can be significantly less (preferably at least 5 times less, more preferably at least 10 times less) than the corresponding pressure drop of a gas flow through the layer of adsorbent material. The '039 Climeworks publication suggests that an advantage of this aspect is a more uniform distribution of pressure gradients across the layer of adsorbent material, and therefore a more uniform distribution of flow through the layer of adsorbent material, which ensures the most efficient utilization of the adsorbent material during the adsorption process.
[0107] In addition to the above, embodiments of the present disclosure provide the advantage of improving uniformity of flow direction by controlling the directionality of inflow and outflow through the adsorbent material layer using, for example, deflected portions or louvers provided at the external support structure.
[0108] According to one embodiment of the '039 Climeworks publication, at least some elements (e.g., stiffeners / rods) of the rigid frame structure supporting the two layers of fabric material located inside the adsorbent layer have an H, C, or Z-shaped profile or similar shape. The '039 Climeworks publication suggests that this example has the following advantages: since the path of potential bypass flow is significantly longer than in the case of straight elements in the adsorbent layer, bypass flow of adsorbent material around the bulk layer that may occur at the edge contained in the adsorbent layer can be reduced (Figure 9 of the '039 Climeworks publication).
[0109] In addition to the above, the present disclosure provides the following advantages: the thickness of the layer of adsorbent material is reduced to less than 0.5 cm (e.g., from 0.1 cm to 0.5 cm, which is thinner than the 0.5 cm to 2.5 cm thickness disclosed in the '039 Climeworks publication) by implementing an external support structure disposed entirely outside the layer of adsorbent material (rather than arranging the support members inside the adsorbent layer as in the '039 Climeworks publication), the external support structure may include deflected portions or shields that are configured to, for example, control the directionality of airflow through the external support structure. Advantageously, the absence of an internal frame structure (such as, for example, an H, C, or Z profile member as disclosed in the '039 Climeworks publication) in the present disclosure beneficially reduces the number of edges included in the adsorbent layer where "bypass flow around the bulk layer of adsorbent material" may occur, as disclosed in the '039 Climeworks publication, which results in the formation of leak paths. Reducing the number of edges beneficially reduces the likelihood of possible leak paths within the structure. While the '039 Climeworks publication attempted to minimize this detrimental effect by using an internal structure with a longer path, the external support concept of the present disclosure completely eliminates this problem.
[0110] According to one embodiment of the '039 Climeworks publication, the layer of adsorbent material and the layer of fabric material encapsulating it are constructed so that the adsorbent material can be filled into the layer through one or more holes, preferably at the edges of the layer of adsorbent material. In this embodiment, elements of a rigid frame structure (e.g., reinforcements / rods) supporting two layers of fabric material are located inside the adsorbent layer and can optionally form individual cells within the adsorbent material layer, these elements having one or more holes through which particulate adsorbent material, preferably having good flowability properties, can pass between the cells during the filling process. In addition, if the heat transfer structure is made of a honeycomb structure, the walls of the individual cells of the honeycomb structure may include holes to connect the cells to each other and facilitate filling the structure with particulate adsorbent material.
[0111] In contrast, in embodiments of the present disclosure, the outer support structure of the layer of adsorbent material may be constructed or configured such that the structure of the layer of adsorbent material may be filled with adsorbent material particles, preferably at the edges of the structure through one or more holes, or from the ends by providing hinged or removable end caps. The outer support structure of the layer provides a significant advantage over the '039 Climeworks publication by eliminating the need for thicker layers and internal reinforcements. Having internal reinforcements in the layer, as disclosed in the '039 Climeworks publication, would require the adsorbent particles to bypass and pass through different areas within the adsorbent layer.
[0112] According to one aspect of the '039 Climeworks publication, a method of producing a layer of adsorbent material comprises filling particulate adsorbent material through one or more holes into a layer enclosed between two layers of fabric material, preferably at the edges of the layer of adsorbent material, preferably using pressurized air for the filling process.
[0113] In contrast, in embodiments of the present disclosure, particulate adsorbent material may be filled from an articulated or removable end cap of an external support structure. It will be appreciated that ease of removal of adsorbent material (for eventual replacement thereof) is an important aspect of an adsorbent bed structure as disclosed herein. Articulated or removable end caps may allow material to be poured out, for example by tilting a module or structure. Since there are no internal obstructions within an external support structure as disclosed herein, adsorbent material may be easily removed and replaced or distributed within a module or structure with relative ease and efficiency.
[0114] According to one embodiment of the '039 Climeworks publication, an enclosure or cage enclosing a stack of layers of adsorbent material is supported by the stack to carry vacuum forces applied externally to the vessel under certain process conditions.
[0115] According to one embodiment of the '039 Climeworks publication, the covers or valves that open and seal the gas inlet side or gas inlet manifold and the gas outlet side or gas outlet manifold may be open over at least 50%, preferably at least 75%, and more preferably at least 90% of the front area of the stack (seen in the direction of gas flow).
[0116] One aspect of the '039 Climeworks publication includes a cyclic adsorption / desorption process for removing components from a gas stream using the aforementioned unit. In a preferred embodiment of the '039 Climeworks publication, the unit is used in a process for removing CO2 from air using an amine-based adsorbent material.
[0117] In a typical cyclic adsorption / desorption process using such a unit according to the '039 Climeworks publication, adsorption can be carried out under ambient conditions, for example in the temperature range of -30-40°C and at an absolute pressure of 0.7 to 1.3 bar. After adsorption of carbon dioxide or carbon dioxide and water vapor, the adsorbent material can be heated to, for example, 50-120°C and by reducing the absolute pressure to, for example, 1-250 mbar. 绝对 (i.e., applying a vacuum) and / or exposing the adsorbent material to a purge gas stream to reduce the partial pressure of CO2 surrounding the adsorbent for regeneration or desorption. If desorption is achieved by heating the adsorbent and applying a vacuum, the entire cyclic process is called a temperature-vacuum swing (TVS) process. If desorption is achieved by heating the adsorbent and exposing it to a purge gas stream, the entire cyclic process is called a temperature-concentration swing (TCS) process.
[0118] In a preferred embodiment of the '039 Climeworks publication, the structure is used in a TVS process for removing CO2 from ambient air. BRIEF DESCRIPTION OF THE DRAWINGS
[0119] The preferred embodiments of the present disclosure are described below in conjunction with the accompanying drawings. The accompanying drawings are only used to illustrate the preferred embodiments of the present disclosure and are not used to limit the present disclosure.
[0120] FIG. 1 (PRIOR ART) shows a cross-section of a principle geometric structure known in the art, comprising layers of particulate adsorbent material, each layer enclosed between two layers of preferably flexible fabric material, arranged in a stack to form gas inlet and outlet passages, as described in the '039 Climeworks publication;
[0121] Figure 1A A cross-sectional view showing the principle geometry of another embodiment of an adsorbent article implementing an external support structure according to examples disclosed herein;
[0122] FIG. 2 (PRIOR ART) shows a cross-sectional view of an example known in the art according to FIG. 1 , wherein the layers of particulate adsorbent material are arranged in a “zigzag” configuration, as found in the '039 Climeworks publication;
[0123] Figure 2A Shown according to Figure 1A A cross-sectional view of an embodiment of the invention wherein the layers of particulate adsorbent material are arranged in a "zigzag" configuration;
[0124] FIG. 3 (PRIOR ART) shows a cross-sectional view of a heat transfer structure placed within a layer of adsorbent material connected to a tube through which a heat transfer fluid may flow, as found in the '039 Climeworks publication;
[0125] FIG. 4 (PRIOR ART) shows a 3D view of one embodiment of a heat transfer structure in the form of a sheet of expanded metal connected to a tube through which a heat transfer fluid may flow, as found in the '039 Climeworks publication;
[0126] FIG. 5 (Prior Art) shows a corrugated heat transfer structure placed within a layer of adsorbent material, wherein the lower and upper peaks of the corrugations serve as mounting surfaces for a fabric material encapsulating the adsorbent material, as found in the '039 Climeworks publication;
[0127] FIG. 6 (PRIOR ART) shows a cross-sectional view of an example known in the art in which the layers of adsorbent material have a rectangular shape and the stack formed by these layers has the form of a rectangular block shape, as found in the '039 Climeworks publication;
[0128] Fig. 6A Another embodiment of an adsorbent article according to examples disclosed herein is shown, wherein a layer of particulate adsorbent material is supported by an external support structure and arranged in a "zigzag" configuration;
[0129] FIG. 7 (PRIOR ART) shows an exploded view of an example known in the art in which the layers of adsorbent material have a hexagonal shape with a central hole and the stack formed by these layers is enclosed in a cylindrical container, as found in the '039 Climeworks publication;
[0130] FIG. 8 (PRIOR ART) shows a cross-sectional view of an example known in the art in which the layers of adsorbent material have the shape of concentric rings and the stack formed by these layers has a cylindrical shape, as found in the '039 Climeworks publication;
[0131] FIG. 9 (PRIOR ART) shows a cross-sectional view of a layer of adsorbent material in which the elements of the rigid framework structure located within the adsorbent layer have the shape of a Z-profile, thereby extending the path length of potential bypass flow, as found in the '039 Climeworks publication;
[0132] FIG. 10 (PRIOR ART) shows a top view of a single adsorbent material layer framework, as found in the '039 Climeworks publication;
[0133] FIG. 11 (Prior Art) shows a cross-sectional view of a single adsorbent material layer framework, as found in the '039 Climeworks publication;
[0134] FIG. 12 (PRIOR ART) shows an adsorption breakthrough curve for an example known in the art, such as found in the '039 Climeworks publication;
[0135] FIG. 13 (PRIOR ART) shows a CO2 desorption stream during the desorption step of a process for extracting CO2 from the atmosphere, as found in the '039 Climeworks publication;
[0136] FIG. 14 (PRIOR ART) shows the CO 2 concentration in the desorption stream during the desorption step of a process for extracting CO 2 from the atmosphere, as found in the '039 Climeworks publication;
[0137] FIG. 15 (Prior Art) shows an example of a "zigzag" stack viewed perpendicular to the direction of air flow, showing mounting screws, wedges and sealing components as found in the '039 Climeworks publication;
[0138] FIG. 16 (Prior Art) shows a stack viewed parallel to the direction of airflow with wedges between the frames to maintain the geometry of the channels under load, as found in the '039 Climeworks publication;
[0139] FIG. 17 (PRIOR ART) schematically illustrates a thermal model for sizing primary and secondary heat transfer structures, as found in the '039 Climeworks publication;
[0140] FIG. 18 (Prior Art) shows the integration of a heat transfer fluid distributor at the return line into a "zigzag" stack, as found in the '039 Climeworks publication;
[0141] FIG. 19 (Prior Art) shows the temperature profiles of a primary heat transfer structure and an expanded metal secondary heat transfer structure during a desorption process, as found in the '039 Climeworks publication;
[0142] FIG. 20 (PRIOR ART) shows a heat transfer structure with fins for improved heat transfer, wherein a) is a view along the tubes of the main exchange system and b) is a side view along the fins, as found in the '039 Climeworks publication;
[0143] FIG. 21 (PRIOR ART) shows a schematic diagram of the production process, wherein a) is the structure before bending as shown, and b) is the final bent structure, as found in the '039 Climeworks publication;
[0144] Fig. 22 shows a cross-sectional view of an adsorbent article having an external support structure according to examples disclosed herein;
[0145] Figures 23A to 23C Various examples of external support structures according to examples disclosed herein are shown (photographic images are to scale).
[0146] Figures 24A to 24D shows an assembly process of an adsorbent article and an external support structure according to examples disclosed herein;
[0147] Fig.25 shows a cross-sectional view of an adsorbent article having an outer support structure arranged in a "zigzag" configuration according to examples disclosed herein;
[0148] Fig.26 shows a cross-sectional view of an adsorbent article having an external support structure having a plurality of external support members attached to a porous fabric layer according to examples disclosed herein;
[0149] Fig.27A and 27B showing a cross-sectional view of an outer support structure of an adsorbent article having a varying interior thickness according to examples disclosed herein;
[0150] Fig.28A and 28B shows a cross-sectional view of an adsorbent article according to examples disclosed herein having regions with adsorbent particles of varying sizes;
[0151] Fig.29 is a SEM image of an expanded polyethylene (ePE) article implemented as a porous fabric layer according to an example disclosed herein (the image is in accordance with the scale marked in the figure);
[0152] Fig.30 is a SEM image of a top view of an expanded polytetrafluoroethylene (ePTFE) article implemented as a porous fabric layer according to examples disclosed herein (the image is to scale);
[0153] Fig.31A and 31B is a cross-sectional view of a layer of adsorbent material including a plurality of nodes and fibrils in an interwoven network;
[0154] Fig.32A and 32B is a cross-sectional view of a layer of adsorbent material comprising a plurality of individual adsorbent particles in a densely packed bed;
[0155] Fig.33 is a SEM image of a top view of a woven fabric, with openings formed between each "thread" of the fabric (the image is to scale);
[0156] Fig.34 yes Fig.30 SEM image of a cross-sectional view of an ePTFE article (the image is to scale);
[0157] Fig.35 is a top view SEM image of a microporous material particle according to an example disclosed herein (the image is in accordance with the scale marked in the figure); and
[0158] Fig.36 Yes Fig.35 A SEM image of a top view of a particle of microporous material is shown (the image is to scale as indicated in the figure). DETAILED DESCRIPTION Definitions and terminology
[0159] This disclosure is not intended to be read in a limiting manner.For example, the terms used in this application should be read broadly in the context of the meaning that one skilled in the art would attribute to such terms.
[0160] With regard to imprecise terms, the terms "about" and "approximately" are used interchangeably to refer to measurements including the measured values and also any measurements that are reasonably (fairly) close to the measured values. As understood and easily determined by a person of ordinary skill in the relevant art, a measurement that is reasonably (fairly) close to the measured value deviates from the measured value by a reasonably small amount. Such deviations may be attributed to, for example, measurement errors, differences in calibration of the measured values and / or manufacturing equipment, human errors in reading and / or setting the measured values, fine-tuning to optimize performance and / or structural parameters in view of differences in the measured values associated with other components, specific implementation scenarios, imprecise adjustments and / or manipulations of objects by humans or machines, and / or the like. In the case where it is determined that a person of ordinary skill in the relevant art will not easily determine a value for such a reasonably small difference, the terms "about" and "approximately" may be understood to be the value plus or minus 10%.
[0161] As used herein, the term "fibril" refers to an elongated material such as a polymer, whose length and width are substantially different from each other. For example, a fibril may resemble a string or fiber, wherein the width (or thickness) is much shorter or smaller than the length.
[0162] The term "node" as used herein describes a point of connection of at least two fibrils, wherein a connection may be defined as a location where two fibrils permanently or temporarily contact one another. In some examples, a node may also be used to describe a volume of material that is larger than a fibril, and a location where a fibril originates or terminates without a clear continuation of the same fibril through the node. In some examples, a node is wider than a fibril but shorter than a fibril.
[0163] As used herein, "node" and "fibril" may be used to describe objects that are typically, but not necessarily, connected or interconnected and, for example, of microscopic size. A "microscopic" object may be defined as an object having at least one dimension (width, length, or height) that is so small that the object or details of the object cannot be seen by the naked eye, or are difficult to observe without the aid of a microscope (e.g., including but not limited to a scanning electron microscope or SEM) or any suitable type of magnification device. Example 1. '039 Climeworks publication of a working example in the form of a rectangular stack
[0164] According to a working example disclosed in the '039 Climeworks publication, the structure consists of rectangular layers of adsorbent material stacked on top of each other to form a rectangular block stack, the stack including inlet channels, outlet channels and adsorbent layers. In this example, the manufacture and assembly of the example is described to illustrate the applicability of the invention as a form of useful product for extracting CO2 from ambient air.
[0165] The individual adsorbent material layers of the '039 Climeworks publication are formed by rigid frame structures, each of which comprises a rectangular frame having a side length of 0.5 m x 0.6 m and a height of 1 cm, made of a stainless steel profile. A top view of such a single frame is shown in FIG. 10 of the '039 Climeworks publication, and a corresponding cross-sectional view is shown in FIG. 11 of the '039 Climeworks publication. The manufacture and assembly of the overall structure comprises the following steps: 1. The frame structure is manufactured by welding stainless steel profiles (for example, for mass production, a frame structure with the same function can also be made by plastic material or aluminum injection molding, which can significantly reduce production costs); 2. Insert the aluminum wire mesh and rubber tube containing the heat transfer fluid into the frame to ensure good heat transfer; 3. Glue a layer of nonwoven fabric material on each side (top and bottom) of the frame structure using a two-component adhesive. 4. Production of adsorbent materials based on amine-modified cellulose fibers following a scaled-up version of the procedure disclosed in WO2012168346A1: a. Separation of cellulose nanofibers from a refined fiber beech wood pulp suspension (see "1. Isolation of cellulose nanofibers" in WO2012168346A1); b. The hydrolyzed 3-aminopropylmethyldiethoxysilane solution was added to a nanofiber suspension having a dry mass content of 3.2%; c. The solution was homogenized and stirred for 2 hours; d. freezing the solution in batches in liquid nitrogen in the form of copper; e. freeze-drying the frozen mixture for 48 hours; f. The dried material was placed in an oven and treated at 120°C under an argon atmosphere; g. compressing and grinding the material to obtain a particulate adsorbent material having an average particle size of about 400 μm; 5. Filling the adsorbent material into the framework structure through the holes and then sealing the holes; 6. Obtain a stable layer of adsorbent material layer. The thickness varies between 1 and 1.5 cm; 7. A total of 26 frames are stacked on top of each other, while distance pieces form inlet and outlet channels; 8. The stack is mounted inside a rectangular true chamber with internal dimensions of 0.55 m x 0.55 m x 0.65 m and having inlet and outlet openings for air flow; 9. A pneumatically actuated butterfly valve is connected to each opening to seal the chamber and open the chamber to the surrounding environment; 10. The inlet opening is connected to a fan to generate air flow during adsorption. Further, the chamber is connected to a vacuum pump to reduce the pressure during desorption and to a thermostat to heat and cool the stack during the individual cycle steps;
[0166] According to the '039 Climeworks publication, in the stack of this example, the total surface area of the adsorbent material layers facing the gas inlet channels is about 8 m 2 Although the designed air flow through the chamber is up to 800m / h 3 , but the average velocity of the air flow through the adsorbent layer is as small as 0.028 m / s. This ensures a very small pressure drop (see Example 2 of the '039 Climeworks publication below).
[0167] In FIG. 1 of the '039 Climeworks publication, a schematic diagram of the principle of an embodiment of this example is shown. In FIG. 6 of the '039 Climeworks publication, a 3-D view of a stack comprising 26 layers of adsorbent material is shown. In FIG. 10 of the '039 Climeworks publication, a top view of one of the frame structures consisting of C-profiles 17 and Z-profiles 12 is shown. In FIG. 11 of the '039 Climeworks publication, a cross-sectional view through the frame structure is shown. Example 2. Determination of the pressure drop through an adsorbent layer stack
[0168] According to the '039 Climeworks publication, the pressure drop experienced by an air flow through a structure made substantially according to the description of Example 1 of the '039 Climeworks publication was experimentally determined for different flow rates. To this end, two butterfly valves were opened and a variable speed fan was attached to the inlet opening, thereby generating different air flow rates through the stack. The flow rate was measured using an in-duct velocity head meter, and the pressure drop across the structure was measured using a differential pressure sensor. The following table shows the pressure drop observed at various volume flow rates:
[0169] According to the '039 Climeworks publication, the design flow rate is up to 800m 3 / h, each cycle requires capturing about 1 kg of CO2 from the air (see Example 3 of the '039 Climeworks publication), with the pressure drop kept below 100 Pa. If the average pressure drop during adsorption is 100 Pa, the pumping work required to capture one ton of CO2 from the atmosphere is about 80 kWh (assuming an average of 70% of the CO2 is captured from the air flow and the fan efficiency is 70%). The energy consumption will correspond to an air ventilation electricity cost of $8 per ton of CO2 (assuming an electricity price of $0.1 per kilowatt-hour), which is within an acceptable range. However, if the pressure drop is as high as 500 Pa, the corresponding electricity cost of $40 for air ventilation will exceed the tolerable limit of an economic process.
[0170] The '039 Climeworks publication suggests that the foregoing illustrates the advantages of the exemplary structures disclosed therein over conventional arrangements of particulate adsorbent material, such as packed or fluidized beds, which are much longer adsorbent packings than in the '039 Climeworks publication and typically introduce pressure drops of several kilopascals to several bars.
[0171] In addition to the above, embodiments of the present disclosure provide the advantage of a more compact construction for a packed bed of particulate adsorbent material by implementing an external support structure having an internal volume in which the particulate adsorbent material can be disposed so that the material can be supported while reducing the thickness of the packed bed (or adsorbent layer) since the thickness is determined by the external support structure. Example 3. Implementation of Example 1 in a cyclic adsorption / desorption process
[0172] According to the '039 Climeworks publication, a structure fabricated substantially according to the description of Example 1 of the '039 Climeworks publication was used in a cyclic temperature-vacuum swing adsorption / desorption process to extract CO2 from ambient air. One cycle of the process took approximately 6 hours and included adsorption (3 hours) and desorption (3 hours) steps.
[0173] During the adsorption step in the '039 Climeworks publication, according to Example 2 of the above-mentioned '039 Climeworks publication, the butterfly valve was opened and air was blown through the structure by a variable speed fan while recording the flow rate. Further, the CO2 content of the air flow before and after the vacuum chamber and its relative humidity were measured using an infrared detector. The relative humidity during adsorption was relatively constant between 35% and 40%. The air flow rate was 750 to 800 m 3 The CO2 concentrations before and after the chamber during adsorption (the "adsorption breakthrough curve") are shown in FIG. 10 of the '039 Climeworks publication.
[0174] According to the '039 Climeworks publication, initially, within the first few minutes of the adsorption process, the CO2 concentration at the outlet of the chamber drops to almost 0 ppm. This demonstrates that the structure of this embodiment has very good performance, because the disappearance of the CO2 concentration indicates that almost all of the air flow through the structure effectively passes through the adsorbent material layers and does not bypass them. If there is a large amount of bypass air blowing, this bypass flow, which still contains about 400 ppm CO2, will mix with part of the air flow that passes through the adsorbent material layers and will increase the CO2 concentration at the outlet of the chamber.
[0175] The '039 Climeworks publication suggests that this behavior of the system is significantly better than that observed in experiments using a short packed bed of adsorbent material 1 cm in length in a conventional 4 cm diameter stainless steel column, in which the outlet CO2 concentration never reached the low values observed in that example, presumably due to flow bypass, since the bed was not secured between two layers of fabric and bypass could have occurred along the column wall.
[0176] In particular, the '039 Climeworks publication suggests that this demonstrates that the structures disclosed in the examples disclosed herein allow for the creation of embodiments based on 3-D structures and embodiments comprising different materials that exhibit advantageous behavior during operation and that cannot be created from prior art extruded 2-D structures.
[0177] In addition to the above, embodiments of the present disclosure provide the advantage of providing a more compact 3-D structure for a packed bed of particulate adsorbent material by implementing an external support structure having an internal volume into which the particulate adsorbent material can be disposed. Beneficially, the thickness of the 3-D structure can be reduced to less than 0.5 cm (e.g., 0.1-0.5 cm, which is thinner than the 1 cm thickness or length of the adsorbent material in the '039 Climeworks publication referenced above) because the thickness is defined by the external support structure.
[0178] Further, the '039 Climeworks publication suggests that the example demonstrates that, using the proposed structure, a large portion of the CO2 contained in a flow of atmospheric air can be extracted using a granular amine-modified adsorbent material at a pressure drop below 100 Pa and that such a structure can be manufactured with reasonable effort.
[0179] In the subsequent desorption step in the '039 Climeworks publication, the vacuum chamber is evacuated to about 100 mbar. 绝对 (absolute pressure of millibars), the stack is subsequently heated to about 85°C by circulating hot water in a plastic tube. Thereafter, the CO2 desorbed from the adsorbent material is continuously pumped out of the chamber by a vacuum pump. The mass flow rate of CO2 leaving the vacuum pump is measured using a calorimetric mass flow meter, see Figure 13 of the '039Climeworks publication. The CO2 concentration is also measured using an infrared sensor, see Figure 14 of the '039Climeworks publication. It was observed that after the air initially still contained in the system was purged, the CO2 concentration reached the saturation limit of the sensor after a desorption time of about 30 minutes, indicating that the CO2 concentration obtained was at least >99%. During the complete desorption step in the '039Climeworks publication, about 1 kg of CO2 was recovered. Therefore, this example further illustrates that the structure of the '039Climeworks publication has been successfully applied to extract CO2 with a purity of >99% from the atmosphere. Example 4. Example with triangular gas inlet and outlet channels
[0180] Another structure is manufactured according to the '039 Climeworks publication, in which the gas inlet and outlet channels between the adsorbent material layers have a triangular cross-section. To this end, 20 frame structures are produced by injection molding of thermoplastic material, each of which defines a 2 cm thick layer of adsorbent material. During the injection molding process, a heat transfer structure consisting of an aluminum tube and an aluminum honeycomb structure is integrated with the frame structure, and the aluminum honeycomb structure has a cell width of 1 / 2 inch, and four of the six side walls of each cell contain a central hole with a diameter of 4 mm. Each frame also includes a triangular edge on its top, which defines the distance between two stacked frames, thereby defining the shape of the gas inlet and outlet channels. After the molding process, a woven (woven) fabric material made of a mixture of PET and PE fibers is glued to both sides of the frame, and the frame is filled with adsorbent material, similar to the filling process described in Example 1 of the '039 Climeworks publication. During the filling process, the adsorbent material passes through the cell network of the aluminum honeycomb structure via the holes in the side walls of the honeycomb cells. Twenty frame structures were then stacked on top of each other to form a stack, the cross section of which is schematically shown in FIG. 2 of the '039 Climeworks publication. Example 5. Use of Flue Gas CO2 Capture Process
[0181] According to the '039 Climeworks publication, a stack of layers of adsorbent material contained in a vacuum chamber is used to capture CO2 contained in a flue gas stream of a natural gas driven cogeneration internal combustion engine, the stack being similar to the stack described in Example 1 of the '039 Climeworks publication.
[0182] According to the '039 Climeworks publication, in this case the CO2 concentration in the gas stream passing through the structure is about 6%. The gas volume flow rate during adsorption is significantly lower, i.e., between 20 and 30 m 3 The adsorption process takes 0.5 hours and extracts on average 90% of the CO2 contained in the gas stream.
[0183] According to the '039 Climeworks publication, the desorption process takes 1 hour, during which the CO2 is removed from the adsorbent material by heating it to 95° C. Three of the units (a unit consists of a stack contained in a vacuum chamber) are operated in series so that at any one time one stack is in adsorption mode and two stacks are in desorption mode, and CO2 can be captured continuously from the flue gas flow. Example 6. Effect of heat exchange structures placed inside the adsorbent material
[0184] According to the '039 Climeworks publication, in order to experimentally demonstrate the effectiveness of the heat transfer structure incorporated within the adsorbent material layer, a packed bed of 100 g of the adsorbent material (see Example 1 in the '039 Climeworks publication) was placed in a rectangular packed bed aluminum reactor of cross-section 60 mm x 60 mm. After 3 hours of adsorption, during which air with a relative humidity of 60% flowed through the reactor at 20 l / min (liters / minute), the reactor was evacuated to 100 mbar by using a vacuum pump. 绝对 The sample was desorbed by heating the reactor wall to 90°C through a jacket filled with water. The temperature in the center of the bed was recorded during the desorption process. For this experiment, the temperature in the center of the bed took 221 minutes to reach 80°C.
[0185] Subsequently, the experiment was repeated according to the '039 Climeworks publication, placing 6 g of 3 / 4 inch cell width aluminum honeycomb structure in the bed of adsorbent material to increase heat transfer. For this experiment, the temperature in the center of the bed took 79 minutes to reach 80°C.
[0186] The '039 Climeworks publication suggests that this observation demonstrates the effectiveness of heat transfer structures included in the bed of adsorbent material, which results in a significant reduction in the time required to heat the bed of adsorbent material during the desorption step, which in turn reduces the overall cycle time, thereby reducing the overall cost of the adsorption process.
[0187] The '039 Climeworks publication suggests that this example further illustrates another advantage of the structures disclosed in the examples disclosed therein over other prior art structures, as 3-D structures that increase heat transfer contained within layers of adsorbent material such as aluminum honeycomb cannot be easily incorporated into prior art extruded 2-D structures.
[0188] In addition to the above, the present invention provides the advantages of reducing the thickness of the adsorbent layer and controlling the direction of gas flow by implementing the external support structure disclosed herein. In addition, there is no internal support structure in the adsorbent layer (such as the honeycomb structure described above in the '039 Climeworks publication), which provides additional benefits, such as the absence of internal structures that may hinder the emptying and refilling process of the adsorbent layer. Example 7. Examples of rectangular stacking forms, describing possible dimensions of the frame and stack and stack components
[0189] According to the '039 Climeworks publication, in view of the requirements for pressure drop, the inlet and outlet channel lengths are limited to 1m, with a maximum adsorbent layer thickness of 1cm and an inlet channel height of 1cm. For construction reasons, the vacuum chamber in which the adsorber structure is housed is limited to contain 500 to 1000kg of adsorbent material. It was found that the width of the resulting frame was 1.45m. The frames were stacked on top of each other in a "zigzag" manner, with an angle of 2° between flat surfaces. In this way, the dead volume (i.e., the stack volume not occupied by the adsorbent material) was reduced by 40% compared to a stack with parallel channels and the same inlet channel height. The reduction in dead volume improves cost efficiency and process efficiency by packing more adsorbent material into a given volume and thus producing more CO2 from a given facility. The resulting stack height is 1.47m, with 88 adsorbent material frames.
[0190] In FIG. 15 of the '039 Climeworks publication, the frames 5 are separated by wedge-shaped spacers 23, which are glued to the frames along the edges of the 1m. These wedge-shaped spacers are used to form the angles of the channels and seal the channels on the sides. Each wedge-shaped spacer is oriented on the head of a screw 24 that is attached to the frame at the thick end. Each spacer is also attached to an adjacent frame, where a screw 25 passes through the adjacent frame and is attached to the next lower wedge-shaped spacer. The wedge-shaped spacers are glued to the frames with double-sided tape to provide uniform adhesion. The sealing strips 8 and 9 seal the channels and thus form the inlet and outlet channels through which the airflow 1 must pass, respectively. Compared with the extraction monomer or welded structure used in the prior art, this assembly solution allows the stack to be highly modular and adaptable. A single or a group of frames can be economically added, removed or replaced without affecting the performance of the entire stack.
[0191] In Figure 16 of the '039 Climeworks publication, the stack is shown from the orientation of the inlet channel. The wedge 26 placed on the main heat transfer structure also supports the inlet channel profile to prevent sagging and maintain the desired width of the inlet channel. In order to ensure that the stacking height of the 88 frames is consistent, the total height of each stacked component needs to be within an acceptable tolerance range. In addition, the bonding between the fabric material and the frame and the wedge and the sealing strip needs to be consistent and uniform. For example, a tolerance of 0.5mm on the thickness of the glue bead on each frame would result in a total offset of 4.4cm in the position and height of the 88 frame stack, which jeopardizes the connection to the heat transfer fluid system, as described in Example 10 of the '039 Climeworks publication. For this purpose, a double-sided tape with a thickness of 0.22mm is used. The tape has a consistent bonding thickness and strength that can withstand temperatures of up to 120°C applied by the desorption process, which facilitates repairs and overhauls and reduces assembly time compared to glue.
[0192] According to the '039 Climeworks publication, the same principles of stacking layout and assembly described in this example can be applied to various other stacking geometries, such as but not limited to smaller stacks consisting of fewer frames, different frame sizes, and non-angled stacking layouts, i.e., stacks in which the frames are substantially parallel to each other and there are no angles between the surfaces, i.e., no "zigzag" structure. Example 8. Low thermal mass frame
[0193] Reducing the thermal mass of the frame per unit mass of adsorbent material contained reduces the overall energy requirement of the desorption process and is a key parameter in the design of DAC systems. Since the desorption process occurs in a vacuum structure that carries the vacuum force, the frame itself must only carry its own weight, the weight of the adsorbent material, the weight of the heat transfer structure, and ensure the desired geometry of the inlet and outlet channels and sealing surfaces. According to the '039 Climeworks publication, an example of such a frame is composed of four aluminum C-profiles with external dimensions of 10×10 mm and internal dimensions of 8×8 mm, connected by edge brackets to form a rectangular form. The main heat transfer structure is formed by 10 (rows) of 8mm outer diameter aluminum pipe pieces, which are placed in the C-profiles and pass through the C-profiles in two places to allow connection with the water distributor. In this way, the stability of the main heat transfer structure is ensured without additional frame components. The aluminum tubes (main heat transfer structure) therefore make a significant contribution to the single body stiffness of the frame. The secondary heat transfer structure is made of expanded aluminum sheet metal, which is formed into the primary heat transfer structure as shown in Figure 5 of the '039 Climeworks publication and glued in place. The fabric material is bonded between the C-profiles at the edges of the frame, thereby forming a closed, air-permeable volume into which the adsorbent material can be filled. In order to prevent bulging when filled with adsorbent, the fabric material is stretched and glued to the tubes of the primary heat transfer structure and the edge profiles of the frame. Thus, a cell of size 1 m x 0.1 m is formed, which is filled with adsorbent material. Each cell is equipped with a sealable hole at one corner of the C-profile for filling with adsorbent.
[0194] According to the '039 Climeworks publication, the thermal mass of the components that must be thermally cycled during the cyclic adsorption-desorption process is a determining factor in the feasibility of the frame design. The contribution of each element is detailed in the table below, along with the total thermal mass of the frame per unit mass of contained adsorbent material. The contained adsorbent mass is 7.25 kg.
[0195] According to the '039 Climeworks publication, an example adsorbent suitable for capturing CO2 from ambient air has a specific heat capacity of 1.4 kJ / K / kg adsorbent, while the specific heat of desorption of CO2 and water is 211 kJ / kg adsorbent material. In a typical desorption process, the adsorbent material must be heated from the adsorption temperature of 20°C to 100°C. It can be determined that the total thermal energy requirement in this typical desorption process is 323 kJ / kg adsorbent material. In this case, the thermal energy requirement of the framework is 30.2 kJ / kg adsorbent material, or 9.3% of the total thermal energy requirement. Example 9. Heat transfer structure and its sizing
[0196] In the '039 Climeworks publication, heat transfer through a representative cell of secondary heat transfer structures and adsorbent material was studied using numerical simulation. A representative cell consisting of a heat transfer structure concentric with the adsorbent cell was studied, as shown in Figure 17 of the '039 Climeworks publication. A temperature boundary condition was applied at one end of the heat transfer structure, which was separated from the cell by a thermal resistance representing the connection between the primary heat transfer structure and the secondary heat transfer structure. Various effects of thermal connection, material and geometry were studied. Among common engineering materials, aluminum was determined to be the most favorable for the selected parameters due to its high thermal conductivity, low density and corrosion resistance. For the desired adsorbent material and the desired desorption process duration, it was found that a cell with a length of 50 mm and an adsorbent cell of 10 mm in diameter could be adequately heated with a secondary heat transfer structure of 1.7 mm in diameter. The heat transfer structure specific gravity produced by such a geometry is 0.2 kg / kg adsorbent material, which is higher than the 0.06 kg / kg adsorbent material described in Example 6. These structures provide high thermal conductivity in the planar direction, are easily formable, and allow for effective integration with primary heat transfer structures.
[0197] The 50mm cell length translates into a spacing of the main heat transfer structure in the form of bent aluminum tubes. Thus, on a 1.5m wide frame, there are 10 aluminum tubes (passages). This solution represents a good compromise between heating density, structural stability, material requirements and thermal mass of the frame.
[0198] The aluminum expanded metal of the selected secondary heat transfer structure is first formed around the primary heat transfer structure to increase the contact area, consistent with the form shown in Figure 5 of the '039 Climeworks publication. Further, the secondary heat transfer structure can be bonded to the primary structure with a high thermal conductivity glue or aluminum brazing. Figure 19 of the '039 Climeworks publication shows the temperature profile of the desorption process in a frame equipped with an expanded metal secondary heat transfer structure that is welded to the pipe fittings of the primary heat transfer structure. In this example, a relatively low heat transfer fluid feed temperature of 93.6°C flows into the primary heat transfer structure. The temperature profile at the surface of the pipe fitting and the middle of the expanded metal between the pipe fittings shows that the temperature of the adsorbent reaches 85°C within a desorption time of 90 minutes. Example 10. Connection to process equipment
[0199] The stack will be connected to a heat transfer fluid system. This is achieved by a heat transfer fluid distributor that is engaged into the main heat transfer structure at each frame, as shown in Figure 18 of the '039 Climeworks publication. By using a heat transfer fluid distributor with a flow cross-section larger than the flow cross-section of the main heat transfer structure, the frames are hydraulically set in parallel and therefore have the same inlet temperature and heat transfer fluid flow rate, thereby ensuring uniform heating and cooling performance. Since the heat transfer fluid distributor must be engaged with the free ends of the pipes of the main heat transfer structure, the vertical position of the individual frames must be well controlled. This is supported by bonding the frame components using double-sided tape with strict thickness tolerances, as described in Example 7 of the '039 Climeworks publication. The heat transfer fluid distributor is made of aluminum to avoid corrosion when combined with the aluminum main heat transfer structure. The heat transfer fluid supply line of the frame inlet distributor is placed at the lowest point, and the heat transfer fluid return line of the frame outlet distributor is placed at the highest point. In this way, the system can effectively purge air. Example 11. Thermal mass of a frame using a fin and tube heat transfer structure in a DAC application
[0200] The thermal mass of a possible fin and tube heat transfer structure in the frame was determined for a 20mm thick layer of adsorbent material. This was compared to a conventional frame structure with a 10mm adsorbent material layer thickness. For reference, the mass and thermal mass of a 10mm frame with a flat expanded aluminum metal heat transfer structure according to the current design is calculated in the following table:
[0201] A 20 mm frame with a finned secondary heat transfer structure will have double the mass for the frame C profile due to the doubled height. The wedge-shaped spacers 23, 26 and sealing strips 9, 8 remain the same (although their overall number in the stack is reduced), and the mass of the primary heat exchanger structure remains the same as the length and diameter of the tubes 11 remain the same. The main changes are made to the secondary heat transfer structure. The table below shows the results for a frame with a 20 mm thick layer of adsorbent material and 14.1 kg of adsorbent material.
[0202] The following assumptions are made: ·Frame width = 1.5m, profile thickness is 1mm Frame length = 1.0m, profile thickness is 1mm Main HEX volume (e.g. in 10 mm adsorption layer) = 3.964e-4m 3 · Secondary HEX 100 fins have a 10mm pitch, aligned to the 1.5m edge, 20mm high, 0.5mm thick, 50% of the surface area perforated = 7.5e-4m 3 ·Sub-HEX mass = 7.5e-4m 3 ×2700kg / m 3 =2.025kg Total volume of adsorbent within the frame = 0.0282m 3 Adsorbent mass = adsorbent density (500kg / m 3 )*Total volume = 14.1 kg
[0203] As seen by this example, the fin and tube heat transfer structure allows the adsorbent material layer to be increased to 20 mm, thereby reducing the thermal mass per unit of adsorbent material per frame by 30%. The gain occurs primarily because the primary heat transfer structure and the wedge spacers and seals do not scale with the adsorbent material layer thickness. External support structure
[0204] Figure 1A An adsorbent article 101 as described above is shown in combination with a plurality of side-by-side external support structures 100. Each external support structure 100 has a layer of adsorbent material 5 enclosed therein to form a module (adsorbent article module) to be implemented in the adsorbent article 101. The external support structure 100 is configured such that it has sufficient rigidity to contain and support particles that may form the layer of adsorbent material 5, as well as to define the shape and configuration of the layer 5, and to maintain the integrity of the layer 5, without relying on internal support components, such as the internal support frame components 7 shown in FIG. 1.
[0205] Figure 2A A plurality of external support structures 100 are shown as viewed from the top of the sorbent article 101. The external support structures 100 are connected to each other via connection locations or features 200 to flexibly vary the separation of each external support structure 100 relative to adjacent external support structures 100.
[0206] Fig. 6A An adsorbent article 101 is shown in which a plurality of external support structures 100 are positioned side by side relative to each other, rather than being stacked on top of each other as shown in FIG6 . A connecting member 200 (e.g., a device that attaches or affixes the external support structures 100 together) holds the external support structures 100 in a zigzag or V-shaped configuration, with each external support structure 100 positioned vertically to receive an air flow, such as Figure 2A Also shown is a head member 600 that can be configured such that the outer support structure 100 can be supportably and sealably interconnected to the head member 600 to facilitate handling of the sorbent article 101 as a single unit, such as during installation and / or replacement of the sorbent article 101 or any component thereof.
[0207] Fig. 22 An example of a portion of an outer support structure 100 is shown. In this example, each outer support structure has a first portion 100A and a second portion 100B opposite the first portion 100A. Each of these portions 100A, 100B can be constructed similarly to each other or differently from each other, as further explained below. Each portion 100A, 100B includes a plurality of base portions 2200, a deflected portion 2202, and openings 2204 formed between the base portions 2200 and the deflected portions 2202. These portions 100A, 100B define an internal volume 2206 therebetween, in which particles forming the adsorbent material layer 5 are housed or enclosed. The openings 2204 have a length L1, while the base portions 2200 have a length L2. L1 can be defined as the distance between two adjacent base portions 2200, while L2 can be defined as the distance between two adjacent openings 2204. The deflected portion 2202 controls the direction of air flow in and out of the interior volume 2206, as shown by the two thick arrows.
[0208] In some examples, lengths L1 and L2 are not the same throughout outer support structure 100 and may vary between various base portions 2200 and deflected portions 2202. For example, deflected portions 2202 may be designed to gather more air (larger openings and larger deflection angles) at locations of outer support structure 100 that receive less air flow. In some examples, other variables may include the size of openings 2204, the spacing between deflected portions 2202, the number of deflected portions 2202 formed, the deflection angle of deflected portions 2202 relative to base portion 2200, etc., and each of these variables may be controlled to increase or decrease air flow, change the directionality of air flow, and / or otherwise appropriately control flow into and out of outer support structure 100.
[0209] Figures 23A to 23C Different configurations of the outer support structure 100 are shown, or more specifically, a single portion (100A or 100B) of the support structure is shown. For example, Fig.23A An external support structure 100 of a "cheese grinder" design is shown, wherein a continuous sheet of rigid material (forming a base portion 2200), such as a polymer composite, metal or plastic (and any other suitable material known in the art), is formed by piercing the surface of the sheet or base portion 2200, and portions of the sheet are permanently deformed, thereby deflecting or convexing relative to the base portion 2200 to form a deflected portion 2202.
[0210] exist Fig. 23B In the figure, the external support structure 100 is shown as a "shutter" (louver) design, which is defined as a continuous sheet of rigid material forming a base portion 2200, in which a plurality of slits are cut in parallel so that portions of the base portion 2200 adjacent the slits are permanently deformed, thereby deflecting or bulging relative to the base portion 2200 to form a deflected portion 2202.
[0211] exist Fig.23C , the outer support structure 100 is shown as a "fishnet" design, which is defined as a continuous sheet of rigid material forming a base portion 2200, in which a plurality of parallel slits are formed, after which the two opposite ends of the sheet are pulled apart via a tensile load from an external source. The tensile force causes the deflected portions 2202 to buckle (bulge) out of the plane that originally defined the sheet, so that a plurality of openings are formed between each deflected portion 2202 and an adjacent base portion 2200, and the deflected portions 2202 break away from the adjacent base portion 2200 in response to the tensile force applied to the sheet.
[0212] Figures 24A to 24D A process of assembling or forming outer support structure 100 according to examples disclosed herein is shown. Fig.24A 2 shows an initial state of the first portion 100A, after the deflected portion 2202 and the opening 2204 are formed relative to the base portion 2200, the first portion 100A may be formed from a single continuous sheet of rigid material as described above. Fig. 24B , the porous laminate material layer 2400 is disposed at the inner surface of the base portion 2200 (i.e., the surface that will face the inner volume 2206 when the outer support structure 100 is fully assembled) to cover the entire inner surface of the base portion 2200. The porous laminate material can be a flexible porous material, can be a loose particulate adsorbent material that is permeable to gas but impermeable to the adsorbent material layer 5, and can be formed using any suitable porous polymer, including but not limited to, for example, expanded polyethylene (ePE) and expanded polytetrafluoroethylene (ePTFE).
[0213] exist Fig.24C In the embodiment, the first part 100A and the second part 100B (which have undergone Fig.24A and 24B The first and second parts 100A and 100B are positioned relative to each other (using a similar process to the first part 100A in FIG. 1 ) such that the porous laminate material layer 2400 of each part faces the porous laminate material layer 2400 of the other part in a mirrored (but reversed) alignment. It should be understood that although the first and second parts 100A, 100B have the same structure in the example shown, in other examples, the parts may use different structures or structural combinations. Once the first and second parts 100A, 100B are properly aligned, the two opposite ends of the parts are connected together using end caps 2402. Although only two end caps 2402A and 2402B are shown, additional end caps may also be appropriately implemented to create a container that defines the internal volume 2206 of the external support structure 100. The end caps 2402 are removable to allow filling with adsorbent particles that form the adsorbent material layer 5, which are encapsulated within the end caps 2402 and the porous laminate material layer 2400, as shown. Fig.24D The pores of the porous laminate layer 2400 are smaller than the size of the sorbent particles to retain the particles within the interior volume 2206, but are also capable of simultaneously allowing air flow through the openings 2204 entering the second portion 100B of the outer support structure 100 and out of the openings 2204 of the first portion 100A (e.g., as Fig. 22 ). The removable end cap 2402 also allows for emptying and refilling of the adsorbent material layer 5 with adsorbent particles. In this configuration, there are no internal structures that hinder the emptying and refilling process.
[0214] Fig.25The outer support structure 100 is shown as seen from the top of the adsorbent article 101. The figure shows the air flow (inflow and outflow) through the adsorbent article 101 (and also through the separate outer support structure 100), so that the air flow is controlled by the angle and shape of the deflected portion 2202, as described above.
[0215] Fig.26 An example of an external support structure 100 is shown, which includes a first portion 100A and a second portion 100B. The first portion 100A includes a plurality of base portions 2200A. The base portion 2200A is either made of a single continuous sheet of material or made of a plurality of separate components that are attached or affixed to each other to form the first portion 100A of the external support structure 100. The first portion 100A also includes a first porous laminate layer 2400A attached thereto. The second portion 100B includes a plurality of base portions 2200B. The base portion 2200B is either made of a single continuous sheet of material or made of a plurality of separate components that are attached or affixed to each other to form the second portion 100B of the external support structure 100. The second portion 100B also includes a second porous laminate layer 2400B attached thereto. The particles forming the adsorbent material layer 5 may be housed between the first portion 100A and the second portion 100B, within the interior volume 2206 defined by the porous laminate material layers 2400A, 2400B and the end caps 2402A, 2402B.
[0216] Fig.27A and 27B An example of the outer support structure 100 is shown when the end caps 2402A, 2402B have different lengths. Fig.27A In the embodiment, the length of the end cap 2402A is longer than the end cap 2402B, and in Fig.27B , the length of end cap 2402A is shorter than that of end cap 2402B, and both define a trapezoidal cross-section of the internal volume 2206.
[0217] Fig.28A and 28BAn example is shown of how the particles forming the adsorbent material layer 5 may vary depending on the area in which they are located within the interior volume 2206 of the outer support structure 100. Thus, the loose particulate adsorbent material may include at least a first group of particles having a first size and a second group of particles having a second size that is smaller than the first size, and in some examples, a third group of particles having a third size that is smaller than the second size. In particular, the example shows particles of three different sizes, where particles 5A (first group) are the largest, particles 5B (second group) are smaller than particles 5A, and particles 5C (third group) are smaller than particles 5A and 5B. In the interior volume 2206, particles 5A occupy area A, particles 5B occupy area B, and particles 5C occupy area C, and area A is located proximal to the longer end cap 2402A, while area C is located proximal to the shorter end cap 2402B, with area B located between the two.
[0218] Advantageously, the different sizes of the sorbent particles allow for more flexible control of air flow through the interior volume 2206. For example, region A having larger sized particles 5A allows air flow from one side of the outer support structure 100 to the other side (i.e., as shown in FIG. Fig.28B As shown, the pressure change (ΔP) between the air flow (in) and the air flow (out) is smaller. Since the cross-sectional thickness "d1" of the adsorbent material layer 5 in region A is larger, the flow path in region A is also longer, but the larger particle size and lower density help reduce the flow resistance therein. For example, region C has the thinnest cross-sectional thickness "d2" of the adsorbent material layer 5, which allows the inclusion of smaller particles to facilitate a higher packing density of particles therein. Therefore, the outer support structure 100 can taper from one end (thickness d1) to the other end (thickness d2), thereby presenting a tapered configuration.
[0219] Although the geometry of the individual particles, the size of the individual particles, and the packing density of the particles may vary from region to region, it should be understood that these parameters can be controlled so that the flow characteristics through two or more regions can be relatively similar. Advantageously, forming these regions with different parameters allows for greater freedom and flexibility in the design and characteristics of the adsorbent layer 5, and also facilitates proper engineering of each component within the adsorbent article 101 to minimize "dead zones" or non-uniform use of adsorbent material. Uniform use of adsorbent material allows all adsorbent particles to degrade fairly and consistently, making it easier to identify when to replace the adsorbent article 101 without wasting adsorbent particles that are still usable when replacing the entire adsorbent article 101.
[0220] Fig.29 and 30An SEM image of the structure of a porous laminate layer 2400 according to some examples using different materials is shown. Nodes 3108, fibrils 3110, and pores, openings, or spacings 3106 are shown, as further explained herein. Fig.29 EPE is shown as the material used as the porous laminate layer 2400. Fig.29 The bottom of the graph shows: “1.0 kV 11.0 mm x 15.0 k SE (UL) 1 / 21 / 2013”, and the distance between the two subsequent lines shown in the lower right corner represents 3.00 μm. Fig.30 ePTFE is shown as the material for the porous laminate material layer 2400. In some examples, the material used for the porous laminate material layer 2400 is hydrophobic to prevent liquid water from entering the interior volume 2206. In some examples, the material is also microporous, having (one or more) pore sizes that are small enough to facilitate air flow therethrough while retaining the adsorbent particles forming the adsorbent material layer 5 within the interior volume 2206. In some examples, the material can withstand repeated heating and cooling cycles and has sufficient durability (e.g., more durable than the adsorbent particles of the adsorbent material layer 5) so that the porous laminate material layer 2400 does not need to be replaced frequently.
[0221] The adsorbent article 101 disclosed herein is more efficient than prior art designs because the module (i.e., the outer support structure 100 containing the loose particulate adsorbent material for gas adsorption) can be refilled rather than just discarded after a single use. The replaceability and reusability of the adsorbent article 101 provides a more environmentally friendly design and improves cost efficiency in the long run. The freedom in design also allows for complete and total use of all loose particulate adsorbent materials in the adsorbent article 101. In addition, using the current structure, a thinner bed or panel of particulate adsorbent material for gas adsorption can be manufactured with a thickness of less than about 5mm, 4mm, 3mm, 2mm, 1mm, 0.5mm, 0.3mm or any other suitable range or value therebetween. Implementing a thinner layer of adsorbent material within the above range helps to reduce the pressure drop across the adsorbent material layer. The lack of internal support in the outer support structure 100 also helps to make it easier to fill and refill the particulate adsorbent material for gas adsorption therein, and when filling or refilling, particles of different sizes can be placed in layers inside the outer support structure 100. In addition, the base portion 2200, deflected portion 2202 and openings 2204 can be adjusted or changed throughout the external support structure 100 for different purposes, including but not limited to: for example, reinforcing large panels, preventing large objects or animals from entering, and considering high or low traffic areas through the internal volume 2206 of the external support structure 100 or within the internal volume 2206.
[0222] Fig.31A , 31B , 32A and 32B show cross-sectional views of an adsorbent material layer 3100 (eg, used as adsorbent material layer 5), which includes a first side 3102 and a second side 3104 through which air flow can pass.
[0223] exist Fig.31A , the adsorbent material layer 3100 includes two portions: a first portion 3101 having a larger pore size, which defines a first side 3102; and a second portion 3103 having a smaller pore size, which defines a second side 3104. The two portions are adjacent to each other so that the second side 3104 is more sealed relative to the more open first side 3102. Each side has a plurality of pores, openings, or spaces 3106, into which foreign particles 3112 of certain sizes can enter (as indicated by white arrows) but are prevented from passing through to the other side. For example, the size of the particles prevented from passing through the layer can be greater than about 10 μm, greater than about 20 μm, greater than about 30 μm, greater than about 40 μm, greater than about 50 μm, or any other suitable range or value therebetween.
[0224] For example, in Fig.31A 3103, the shape and size of the pores 3106 in each of the different portions 3101 and 3103 can be defined by a plurality of nodes 3108 and fibrils 3110 that can connect two or more nodes together such that the nodes 3108 and fibrils 3110 prevent foreign particles 3112 larger than a certain size from passing through the layer 3100. For example, foreign particles 3112 that enter the first portion 3101 can be prevented from entering the second portion 3103, thereby preventing the foreign particles from passing through the adsorbent material layer 3100. The foreign particles 3112 can be trapped inside the pores 3106 of the first portion 3101 or released into the external environment through the first side 3102 from which they enter. The nodes 3108 and fibrils 3110 can be contained within a frame or external support structure 100 (not shown).
[0225] The nodes and fibrils referred to herein may be part of a non-woven microporous material having interconnected nodes and fibrils that operate together to prevent certain sizes of foreign particles from passing through the layer 3100 while still allowing air flow to pass through. Preventing such particles from passing through maintains the purity of the contained particles, as well as preventing sorbent particles from passing through the packaging layers to exit, preventing foreign particles from passing through the layers to enter the packaging, and maintaining purity even as the structure flexes and moves.
[0226] For example, in Fig.31BIn the embodiment of the present invention, the adsorbent material layer 3100 may be provided with an additional portion, namely the third portion 3105, which has a smaller pore size than the first portion 3101, thereby sandwiching the first portion 3101 between two portions (3103 and 3105) having a smaller pore size than the first portion 3101. The third portion 3105 also has pores, openings or spaces 3106, as well as nodes 3108 and fibrils 3110. In this configuration, the first side 3102 is defined by the third portion 3105 and the second side 3104 is defined by the second portion 3103, so that foreign particles 3112 that may have entered the adsorbent material layer 3100 from one side will be captured and / or fixed in the pores 3106 of the first portion 3101 and prevented from passing to the other side.
[0227] In some examples, the particles trapped in the pores 3106 of the first portion 3101 may be adsorbent particles to maintain the purity of the adsorbent particles contained as described above. The adsorbent particles may be provided into the pores 3106 of the first portion 3101, and then the second portion 3103 and the third portion 3105 are successively formed on two opposite sides to trap the particles therein. The adsorbent particles may be provided in the form of dry particles, entrained by a forced flow (e.g., along the Fig.31A The adsorbent material is directed in the direction of the white arrow in the figure and introduced through the more open first side 3102 and then captured on the more sealed second side 3104 and located between the nodes and fibrils of the first portion 3101 of the adsorbent material layer 3100, thereby retaining the adsorbent material within the pores 3106 of the first portion 3101.
[0228] For example, in Fig.32A and 32B In the embodiment of the present invention, the shape and size of the pores 3106 can be defined by a plurality of individual particles 3200 of the adsorbent material. The adsorbent particles 3200 can be contained within a frame or external support structure 100 so as to maintain a packed bed in which the particles 3200 are tightly packed (packed) to prevent foreign particles (not shown) from passing through the layer 3100 while still allowing air flow therethrough. The frame 100 can be compressible to fit with the outer support structure 100. Fig.32A The less compressed (or more expanded) packed bed shown is formed as compared to Fig.32B A more compressed packed bed is shown. A more compressed or more compact packed bed may result in a lower void fraction (the pores 3106 defined therein) and reduced gas accessibility compared to a less compressed or less compact (or more expanded) packed bed. The void fraction is the relative ratio of the void volume of a region to the total volume of the region. Thus, due to Fig.32B The diffusion distance ratio Fig.32A is shorter, so the initial kinetics of gas adsorption to the adsorbent material layer 3100 may be faster, but Fig.32BThe time for CO2 adsorption to reach equilibrium in the adsorbent material layer 3100 will be longer than Fig.32A The time in increases.
[0229] Fig.33 is an SEM image of a woven fabric with openings formed between each fabric "thread". Due to the size of these openings, foreign particles can enter through the fabric, while internal particles can leave the fabric through these openings. Fig.34 is a SEM image of a cross-sectional view of a nonwoven microporous material (with Fig.30 ), for example, Fig.31A and 31B The material of the adsorbent material layer 3100 shown in FIG. 3 shows nodes 3108, fibrils 3110, and pores, openings, or spaces 3106 formed therebetween. Fig.30 and 34 The bottom of the diagram shows: "5.0kv 13.3μ". In some examples, Fig.33 Fabric and Fig.34 Nonwoven (woven) materials of the same or similar air flow rate, ΔP measurement and / or void fraction measurement. The flow through the fabric may be due to the large through-void features, while the flow through the nonwoven material may be due to a large number of small but interconnected void features (e.g., internal pores, openings or spacing).
[0230] Fig.35 is a top view SEM image of a microporous material particle, such as Fig.32A and 32B Particles 3200 are shown forming a layer of adsorbent material 3100, where the particles may be of different and variable sizes and shapes or configurations. Some particles may be larger or smaller than others, and some particles may be more rounded or less rounded than others. On the bottom of the image is displayed: "2.9kV 10.8mm x 200LM (UL) 6 / 25 / 2020". The distance between the two continuous white lines shown in the lower right corner represents 200μm. Fig.36 yes Fig.35 Another SEM image of a top view of a microporous material particle is shown, but at a greater magnification, where the distance between the two continuous white lines shown at the lower right corner represents 20 μm. On the bottom of the image it is shown: "2.0 kV 10.8 mm x 2.50 k LA80 (UL) 6 / 25 / 2020".
[0231] Reference numerals list 1 Inlet gas flow, gas inflow, main gas inflow direction 2 Outlet gas flow, gas outflow, main gas outflow direction 3 Gas inlet channel 4 Gas outlet channel 5 Granular adsorbent material layer 6. Sheet of fabric material encapsulating adsorbent material 7 A portion of the frame that defines the geometry of the adsorbent layer and supports the fabric material that encapsulates the adsorbent material 8 Structure for blocking the end of the gas inlet passage 9 Structure that blocks the starting point of the gas outlet passage 10 Secondary heat transfer structure inside the adsorbent material layer 11 Tubes containing heat transfer fluid that are part of the main heat transfer structure inside the adsorbent material layer 12 Z-profile, which is part of the framework that defines the geometric structure of the adsorbent layer 13. Bypass gas flow path within the adsorbent material layer and along the edge of the packed bed of adsorbent material 14 A container enclosing a stack of layers of adsorbent material 15 Gas outlet manifold 16 Valve / cover, which opens and seals the outlet manifold from the environment 17 C profile, which is part of the frame that defines the geometric structure of the adsorbent layer 18 Entrance face 19 Exit surface 20 Heat transfer structure in thermal models 21 Adsorbent Materials in Thermal Models 22 Thermal Contact Resistance in Thermal Models 23 Spacers forming wedges at the edges 24 Mounting screws 25 Mounting and orientation screws 26 A spacer that forms a wedge on 27 Heat transfer fluid distributor 28 Heat transfer fluid return line 100 External support structure 200 Flexible connection parts or components 2200 Base part 2202 Deflected Part 2204 Opening 2206 Internal volume 2400 porous laminate layer 2402 End Cap 3100 Adsorbent material layer 3101 Part 1 3102 First side 3103 Part 2 3104 Second side 3105 Part 3 3106 Pores or openings 3108 nodes 3110 Fibril 3112 Foreign particles 3200 Adsorbent particles d Distance between 18 and 19 d1 Maximum cross-sectional thickness of the adsorbent material layer d2 Smaller cross-sectional thickness of the adsorbent material layer Tb Temperature boundary in thermal model L Distance between fin groups
Claims
1. A gas separation unit for separating a first gas from a mixture comprising the first gas and other gases different from the first gas using a cyclic adsorption / desorption process using a loose particulate adsorbent material for gas adsorption: in, The particulate adsorbent material is arranged in at least two stacked layers, wherein each layer comprises two sheets of a flexible porous material that is breathable but impermeable to a loose particle adsorbent material, and wherein the loose particle adsorbent material: (1) disposed within an interior volume of and supported by an outer support structure, the outer support structure comprising a plurality of base portions, deflected portions, and openings therebetween, (2) being arranged substantially in parallel so as to define an inlet face of the layer and an outlet face of the layer, (3) the distance between the sheets is set to be in the range of 0.1 to 2.5 cm, and (4) an encapsulated cavity in which the particulate adsorbent material is located, wherein the cell has a gas inlet side or gas inlet manifold through which an inflow of a gas mixture enters the cell, and a gas outlet side or gas outlet manifold through which an outflow of a gas mixture leaves the cell, a gas path between the inflow and the outflow being restricted in the cell to pass through at least one layer, wherein the directionality of the inflow and the outflow through the outer support structure is controlled by the deflected portion of the outer support structure; wherein each of the layers is arranged in the unit such that the inlet flow passes through the inlet face, then passes through the particulate adsorbent material located in the cavity of the respective layer, and then exits the respective layer through the outlet face to form the gas outflow; wherein the layers are arranged such that the inlet faces of adjacent layers face each other, thereby enclosing a gas inlet passage, and such that the outlet faces face each other, thereby enclosing a gas outlet passage; wherein the average distance between the inlet face and / or the outlet face of the channel is defined to be in the range of 0.5-5 cm, measured in a direction substantially perpendicular to the main gas inflow direction and the main gas outflow direction, respectively; wherein the length of the inlet face and / or the outlet face in a direction parallel to the main gas inflow direction and the main gas outflow direction, respectively, is at least ten times greater than the distance (d) between the sheets in the layer; and At least one layer, or most layers, or all layers are provided with a primary heat exchange element in the form of a tube containing a heat exchange fluid, combined with a secondary heat exchange element to increase heat transfer between the adsorbent material and the heat exchange element.
2. The unit according to claim 1, characterized in that The base portion and the deflected portion of the outer support structure are formed from a continuous sheet of rigid material.
3. The unit according to claim 2, characterized in that The outer support structure forms a cheese grater, a shroud or a fishnet structure.
4. The unit according to claim 1, characterized in that The multiple base portions are separate components that are attached or secured to each other.
5. The unit according to any one of claims 1 to 4, characterized in that The loose particulate sorbent material includes at least a first group of particles having a first size and a second group of particles having a second size smaller than the first size.
6. The unit according to claim 5, characterized in that The first group occupies a first area within the interior volume, and the second group occupies a second area within the interior volume that is different from the first area.
7. A unit according to claim 5 or 6, characterized in that The outer support structure has a tapered configuration.
8. A unit according to any one of claims 1 to 7, characterised in that The outer support structure includes at least one end cap through which the loose particulate sorbent material is provided to fill the support structure.
9. A unit according to any one of claims 1 to 8, characterized in that The length of the inlet face and / or the outlet face in a direction parallel to the main gas inflow direction and the main gas outflow direction, respectively, is at least 40 times greater than the distance (d) between sheets in the layer.
10. The unit according to any one of claims 1 to 9, characterized in that The flexible porous material includes a hydrophobic material.
11. The unit according to claim 1, characterized in that More than five (5) floors are are stacked substantially parallel to one another in said unit; Alternatively, the stacking is performed at a relative inclination angle in the range of 0.2-15°, the corresponding inlet channels converge along the main gas inflow direction, and the corresponding outlet channels widen along the main gas outflow direction.
12. The unit according to claim 1, characterized in that The layers are substantially planar structures stacked parallel to each other, or wherein the layers are substantially cylindrical structures arranged concentrically with each other.
13. The unit according to claim 1, characterized in that A plurality of spacers are located within the layer.
14. The unit according to claim 1, characterized in that The primary or secondary heat exchange element also acts as a frame structure supporting the sheet of flexible porous material.
15. The unit of claim 1, wherein: A further secondary heat exchange element is provided based on an expansion material.
16. The unit of claim 1, wherein: The loose particulate adsorbent material is an amine-modified particulate material.
17. The unit of claim 1, wherein: The outer support structure is provided with holes into which the loose particulate adsorbent material is filled and the openings of the holes are closed after filling with the adsorbent material.
18. The unit of claim 1, wherein: The unit comprises a surrounding cage which is gas-tight except for a gas inlet opening for the inflow and a gas outlet opening for the outflow.
19. The unit of claim 1, wherein: The sheets of each layer are positioned with a distance between layers ranging from 0.5 to 1.5 cm, or wherein, The average distance between adjacent inlet faces or outlet faces measured in a direction substantially parallel to the main gas inflow direction and the main gas outflow direction, respectively, is in the range of 0.5-1.5 cm.
20. The unit of claim 1, wherein: The length of at least one of the inlet face or the outlet face in a direction parallel to the main gas inflow direction and the main gas outflow direction, respectively, is at least 80 times greater than the distance (d) between sheets in the layer.
21. The unit of claim 1, wherein: The flexible porous material is a flexible fabric material, which is a woven or non-woven textile material based on polymer fibers or yarns, including polymer fibers or yarns based on at least one of ePTFE, ePE, PET or PE.
22. The unit of claim 1, wherein: More than 20 floors are: By using a stack of corresponding external support structures, stacked substantially parallel to each other in the unit; or The stacking is performed at a relative inclination angle in the range of 0.5-10°, the corresponding inlet channels converge along the main gas inflow direction, and the corresponding outlet channels widen along the main gas outflow direction, wherein the inlet channel is closed at its downstream end by the lateral edges of the adjacent layers in contact, and Therein, the outlet channel is closed at its upstream end by the lateral edge of the adjacent layer.
23. The unit of claim 1, wherein: Spacers are located within the layers, the spacers being rigid bar or track structures, including T-, H-, C- or Z-shaped bar structures, or provided by joints or seams between the sheets.
24. The unit of claim 1, wherein: The primary heat exchange element or the secondary heat exchange element also serves as a frame structure supporting the flexible porous material sheet.
25. The unit of claim 1, wherein: The secondary heat exchange element is based on expanded metal, including corrugated expanded metal.
26. The unit of claim 1, wherein: The loose particulate adsorbent material is an amine-modified particulate material based on amine-modified nanofibrillated cellulose having an average particle size in the range of 60 to 1200 μm for adsorbing carbon dioxide.
27. The unit of claim 1, wherein: It comprises a surrounding cage, which is made of a flexible material or a rigid material, is gas-tight except for a gas inlet opening for the inflow and a gas outlet opening for the outflow, and is attached to a vacuum unit for a desorption process, wherein the inlet opening and / or the outlet opening are provided with a controllable cover or valve for changing between adsorption and desorption phases.
28. The unit of claim 1, wherein: The loose particulate sorbent material is arranged with a distance between the sheets in the range of 0.1-0.5 cm.
29. A method of extracting carbon dioxide from air or flue gas in a cyclic adsorption / desorption process using a loose particulate adsorbent material for gas adsorption, comprising: Adsorption of carbon dioxide, or carbon dioxide and water vapour, using the unit of claim 1, wherein the adsorption takes place at a temperature in the range of -30-40°C and at a pressure of 0.7 to 1.3 bar absolute, and After adsorbing carbon dioxide or carbon dioxide and water vapor, the adsorbent material is desorbed by heating to 50-120° C. and reducing the partial pressure of CO 2 surrounding the adsorbent material by reducing the absolute pressure and / or exposing the adsorbent material to a purge gas stream.
30. A gas separation unit for separating a first gas from a mixture comprising the first gas and another gas different from the first gas using a cyclic adsorption / desorption process using a loose particulate adsorbent material for gas adsorption: in, The particulate adsorbent material is arranged in at least two stacked layers, Each layer comprises two sheets of flexible porous material, the flexible porous material is breathable but impermeable to loose particle adsorbent material, and the loose particle adsorbent material: (1) disposed within an interior volume of and supported by an outer support structure, the outer support structure comprising a plurality of base portions, deflected portions, and openings therebetween, (2) being arranged substantially in parallel so as to define an inlet face of the layer and an outlet face of the layer, (3) the distance between the sheets is set to be in the range of 0.1 to 2.5 cm, and (4) an encapsulated cavity in which the particulate adsorbent material is located, wherein the cell has a gas inlet side or gas inlet manifold through which an inflow of a gas mixture enters the cell, and a gas outlet side or gas outlet manifold through which an outflow of a gas mixture leaves the cell, a gas path between the inflow and the outflow being restricted in the cell to pass through at least one layer, wherein the directionality of the inflow and the outflow through the outer support structure is controlled by the deflected portion of the outer support structure; wherein the layers are arranged in a unit such that the inlet flow passes through the inlet face, then passes through the particulate adsorbent material located in the cavity of the respective layer, and then exits the respective layer through the outlet face to form the gas outflow. wherein the layers are arranged such that the inlet faces of adjacent layers face each other, thereby enclosing a gas inlet passage, and such that the outlet faces face each other, thereby enclosing a gas outlet passage; wherein the average distance between the inlet face and / or the outlet face of the channel is defined to be in the range of 0.5-5 cm, measured in a direction substantially perpendicular to the main gas inflow direction and the main gas outflow direction, respectively; wherein the length of the inlet face and / or the outlet face in a direction parallel to the main gas inflow direction and the main gas outflow direction, respectively, is at least ten times greater than the distance (d) between the sheets in the layer; and wherein pipes are arranged in each layer, wherein stackable frame elements are provided, wherein a unit for fluid-transferring attachment at the end of a tube is provided in or at the stackable frame element, and Therein, the stackable skeleton elements are connectable to each other to transfer heat transfer fluid to and from the tubes in the individual layers.
31. A gas separation unit for separating a first gas from a mixture comprising the first gas and another gas different from the first gas by using a cyclic adsorption / desorption process using a loose particulate adsorbent material for gas adsorption, wherein The particulate adsorbent material is arranged in at least two stacked layers, in, each layer comprises two sheets of a flexible porous material, the flexible porous material being permeable to air but impermeable to the loose particulate adsorbent material, and the loose particulate adsorbent material being disposed within an interior volume of and supported by an outer support structure, the outer support structure comprising a plurality of base portions, deflected portions and openings therebetween, the outer support structures being disposed substantially in parallel, defining an inlet face of the layer and an outlet face of the layer, the outer support structures being disposed such that the distance between the sheets is in the range of 0.1-2.5 cm and enclosing a cavity in which the particulate adsorbent material is located, wherein the cell has a gas inlet side or gas inlet manifold through which an inflow of a gas mixture enters the cell, and a gas outlet side or gas outlet manifold through which an outflow of a gas mixture leaves the cell, a gas path between the inflow and the outflow being restricted in the cell to pass through at least one layer, wherein the directionality of the inflow and the outflow through the outer support structure is controlled by the deflected portion of the outer support structure; wherein each of the layers is arranged in the unit such that the inlet flow passes through the inlet face, then passes through the particulate adsorbent material located in the cavity of the corresponding layer, and then leaves the corresponding layer through the outlet face to form the gas outflow; wherein the layers are arranged such that the inlet faces of adjacent layers face each other, thereby enclosing a gas inlet passage, and such that the outlet faces face each other, thereby enclosing a gas outlet passage; wherein the average distance between the inlet face and / or the outlet face of the channel is defined to be in the range of 0.5-5 cm, measured in a direction substantially perpendicular to the main gas inflow direction and the main gas outflow direction, respectively; wherein the length of the inlet face and / or the outlet face in a direction parallel to the main gas inflow direction and the main gas outflow direction, respectively, is at least ten times greater than the distance (d) between the sheets in the layer; and wherein tubing is provided in each layer, wherein stackable skeletal elements are provided in or as part of the external support structure, wherein means for fluid transfer attachment of the ends of the tubes are provided in or at the stackable skeletal elements, wherein the stackable skeletal elements are capable of being connected to one another directly or via further tubing, including the use of O-rings, to transfer heat transfer fluid to and from the tubes in each individual layer, wherein the stackable skeletal elements are cylindrical elements having a diameter in the range of 1 to 5 cm, and wherein during the injection molding process, tubing of the primary heat exchange structure as well as the secondary heat exchange structure can be directly included in the external support structure.
Citation Information
Patent Citations
Filter for purifying exhaust gases
EP0766993A2
Low-pressure drop structure of particle adsorbent bed for adsorption gas separation process
US10427086B2
Removal of carbon dioxide from air
US20090120288A1
Carbon dioxide capture / regeneration method using vertical elevator
US20120174778A1
Filter for gases
US6379437B1